A polysulfone-based hollow fiber microfiltration membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202611280444.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-22
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]但现有技术中有的聚砜类灌流膜无法高精度的截留细胞或无法及时排出代谢物,影响灌流培养的正常进行,有的聚砜类灌流膜存在第一表面容易形成滤饼层,造成膜孔堵塞、跨膜压差持续上升、代谢物排出速度出现直线下降,使得灌流培养不能长期稳定运行,即现有技术中有的聚砜类灌流膜无法保障细胞高密度、高活率地生长
[0113]1、本发明科学调控聚砜类的中空纤维微滤膜的第一表面由沟壑状孔洞和支撑纤维组成,通过控制支撑纤维的SEM平均直径、支撑纤维的SEM平均直径与沟壑状孔洞的SEM平均短径的比值、沟壑状孔洞内流通孔的SEM孔径、微滤膜的IPA完全出泡点在合理的范围内、且支撑纤维的长度方向与膜的长度方向相垂直,制得的聚砜类的中空纤维微滤膜能够用于灌流培养,且用于N-1级灌流培养时获得的细胞密度高、细胞活率高。
Smart Images

Figure CN122999009A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane materials technology, and more specifically to a polysulfone-based hollow fiber microfiltration membrane, its preparation method, and its application. Background Technology
[0002] In the industrial production of biopharmaceuticals such as monoclonal antibodies, fusion proteins, and recombinant proteins, upstream cell culture is a core and critical process for obtaining raw materials for biopharmaceuticals. The capacity and efficiency of cell culture directly determine the production cost of biopharmaceuticals and are the core foundation for achieving large-scale, low-cost industrial production of biopharmaceuticals. ATF (alternating tangential flow) perfusion culture has become a core technology for cell culture due to its advantages such as high cell retention rate and long-term stable operation.
[0003] The core component of ATF perfusion culture is the perfusion membrane (mainly hollow fiber membrane). Based on the principle of tangential flow filtration, it traps cells on the inner surface of the membrane (i.e., the first surface of this invention) while simultaneously allowing cell metabolites to be discharged and fresh culture medium to be replaced, maintaining the stability of the cell culture system and ensuring high-density, high-viability cell growth. The microstructure of its first surface directly determines the stability and continuity of the ATF perfusion culture process. Currently, polysulfone polymers (such as polysulfone and polyethersulfone) are the preferred substrate for perfusion membranes used in ATF perfusion culture due to their advantages such as high mechanical strength, good chemical stability, high-temperature resistance, and excellent biocompatibility.
[0004] However, some polysulfone perfusion membranes in the existing technology cannot accurately retain cells or remove metabolites in a timely manner, affecting the normal progress of perfusion culture. Some polysulfone perfusion membranes are prone to forming a filter cake layer on the first surface, causing membrane pore blockage, continuous increase in transmembrane pressure difference, and a linear decrease in the rate of metabolite removal, making it impossible for perfusion culture to operate stably for a long time. In other words, some polysulfone perfusion membranes in the existing technology cannot guarantee high-density and high-viability cell growth.
[0005] Therefore, in order to meet the growing market demand for biopharmaceuticals, it is urgent to develop more polysulfone-based hollow fiber microfiltration membranes with different structures to solve the problem of how to obtain high-density and high-viability cells when using polysulfone-based hollow fiber microfiltration membranes for perfusion culture. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a polysulfone-based hollow fiber microfiltration membrane, its preparation method, and its application. By controlling the composition of the first surface as grooved pores and supporting fibers, the diameter of the supporting fibers, the ratio of the diameter of the supporting fibers to the minor diameter of the grooved pores, the pore size of the flow holes within the grooved pores, the perpendicularity of the length direction of the supporting fibers to the length direction of the membrane, and the complete bubble point of the IPA of the microfiltration membrane, the prepared hollow fiber microfiltration membrane can be used for perfusion culture, and when used for N-1 stage perfusion culture, it achieves high cell density and high cell viability.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a polysulfone hollow fiber microfiltration membrane, comprising a main body, one side of which is a first surface facing the inner cavity, and the other side of which is a second surface. The first surface is composed of grooved pores and supporting fibers. The ratio of the SEM average diameter of the supporting fibers to the SEM average minor axis of the grooved pores is 0.55-0.85; the SEM average diameter of the supporting fibers is 8μm-25μm; the grooved pores have a plurality of flow holes, the SEM pore size of which is no greater than 5μm; the length direction of the supporting fibers is perpendicular to the length direction of the membrane; and the IPA complete bubble point of the microfiltration membrane is 8psi-20psi.
[0008] When hollow fiber microfiltration membranes are used for ATF perfusion culture, the most common methods are N-1 stage perfusion and N-stage perfusion. N-1 stage perfusion involves only cell culture and basically does not involve protein expression, while N-stage perfusion includes both cell culture and protein expression (in the early stage, cell culture is the main process and protein expression is basically not involved, while in the later stage, cell culture and protein expression occur simultaneously). In the cell culture process of N-1 stage perfusion, the feed solution mainly includes cells, metabolites, nutrient solution, etc. When the feed solution passes through the inner space of the hollow fiber microfiltration membrane, small molecules such as metabolites and nutrient solution pass through the first surface of the hollow fiber microfiltration membrane, then through the membrane wall, and finally through the second surface of the hollow fiber microfiltration membrane, while cells are retained on the first surface of the hollow fiber microfiltration membrane. If the first surface structure of a hollow fiber microfiltration membrane is not properly designed, on the one hand, cells may not be retained with high precision, resulting in the loss of seed cells, and the lost cells will clog the membrane pores; on the other hand, cells are prone to deposition on the first surface (achieving "contact" between the cells and the first surface). The deposited cells cannot return to the feed solution in time under shear force (achieving "anchoring" of the cells on the first surface), and the deposited cells will further adsorb other cells in the feed solution (achieving "growth" of the cells on the first surface). Finally, under the action of transmembrane pressure difference, they will be continuously compacted to form an irreversible filter cake layer, which will also lead to pore blockage. Both of these aspects will lead to a decrease in the rate of metabolite excretion, and metabolites will easily accumulate in the culture system, causing the system's microenvironment to deteriorate, inhibiting cell growth and reducing cell viability, and making it impossible to obtain high-density, high-viability cells.
[0009] Through continuous research, we have discovered that the first surface consists of grooved pores and supporting fibers. When the ratio of the average SEM diameter of the supporting fibers to the average SEM minor axis of the grooved pores, the average SEM diameter of the supporting fibers, the pore size of the flow holes within the grooved pores, and the complete bubble point of the microfiltration membrane's IPA are all within a reasonable range, and the length direction of the supporting layer fibers is perpendicular to the length direction of the membrane, it can effectively reduce the formation of the filter cake layer, achieve high-precision cell retention, and timely removal of metabolites, enabling continuous and effective perfusion culture. Simultaneously, it yields high cell density and high cell viability. Specifically:
[0010] Firstly, the first surface of this invention is composed of supporting fibers and grooved pores, forming an alternating surface morphology. Since the length direction of the supporting fibers is perpendicular to the length direction of the membrane, the feed liquid flows along the width direction of the supporting fibers. When the feed liquid passes through the first surface of the hollow fiber microfiltration membrane, the flow path of the feed liquid is a continuous alternation of supporting fibers-grooved pores-supporting fibers-grooved pores, that is, the flow path of the feed liquid presents a concave-convex curve shape. The concave-convex curve shape of the flow trajectory allows the feed liquid itself to generate a certain small shear force. This small shear force causes less damage to cells, but it can provide the driving force for the feed liquid to continue flowing forward, making it difficult for cell molecules to be adsorbed on the first surface. Even if they stay briefly, the binding force between the cells and the first surface is weak, providing a certain basis for not forming a filter cake layer. In addition, the pores on the first surface are grooved pores, which have a larger surface area than non-grooved pores, increasing the outflow channels for metabolites, etc., and providing a certain basis for the rapid discharge of metabolites, etc.
[0011] Secondly, the SEM average diameter of the supporting fibers in this invention is slightly coarse. Simultaneously, the microfiltration membrane of this invention is prepared from polysulfone compounds, which inherently possess good strength. The synergistic effect of the coarser supporting fibers and the polysulfone compounds facilitates obtaining suitable compressive strength on the first surface, providing a foundation for continuous perfusion culture. At the same time, the SEM average diameter of the supporting fibers is not particularly coarse. With the synergistic effect of the length direction of the supporting fibers being perpendicular to the thickness direction of the membrane, when cells come into contact with the supporting fibers, the binding force between the cells and the supporting fibers is relatively weak under the shear force generated by the feed solution itself. Furthermore, even if adjacent cells adsorbed on a single supporting fiber connect along the membrane's length direction, the height of the connected cells is relatively low (not exceeding the diameter of the supporting fiber). In other words, under relatively small shear forces, cells adsorbed on the supporting fibers can be easily connected. Cell detachment from the supporting fibers reduces cell "contact" and "anchoring" on the supporting fibers at the source, resulting in less cell damage and facilitating effective cell culture. If the average SEM diameter of the supporting fibers is too large, while it provides better compressive strength to the first surface, the height of the cells formed after adsorption on a single supporting fiber is also greater. This means the area of the adsorption layer on the supporting fibers is larger, requiring significant shear force to detach the adsorption layer from the supporting fibers. However, this significant shear force can damage the cells in the reaction system, hindering effective cell culture and preventing the acquisition of high-density, high-viability cells. Conversely, if the average SEM diameter of the supporting fibers is too small, the supporting effect on the first surface is weaker, preventing prolonged perfusion culture and also hindering the acquisition of high-density cells.
[0012] With a slightly larger SEM average diameter for the supporting fibers, and a synergistic effect between the ratio of the supporting fiber's SEM average diameter to the SEM average minor axis of the grooved pores (0.55-0.85), and further synergistic effect with polysulfone compounds, the supporting fibers can better support the grooved pores. This means the first surface has decent compressive strength, allowing for prolonged perfusion culture. This ratio also facilitates obtaining a suitable number of grooved pores, promoting timely removal of metabolites. Furthermore, if the ratio of the supporting fiber's SEM average diameter to the SEM average minor axis of the grooved pores is... If the ratio is too small, the average short diameter of the corresponding groove-like pores in SEM will be too large, and the supporting fibers will not be able to support the groove-like pores well, resulting in low compressive strength of the first surface, making it impossible to continue perfusion culture and obtain high-density cells. Similarly, if the ratio of the average diameter of the supporting fibers in SEM to the average short diameter of the groove-like pores in SEM is too large, the average short diameter of the corresponding groove-like pores in SEM will be too small, meaning that there are fewer channels for the discharge of metabolites, resulting in more residual metabolites in the culture system, making cell culture ineffective and unable to obtain high-density and high-viability cells.
[0013] Thirdly, the groove-like pores contain several flow pores that allow for the discharge of metabolites. The SEM pore size of these flow pores can be controlled to be no larger than 5 μm, meaning the pore size is smaller than the cell size. When cells flow into the flow pores within the groove-like pores, the pores can intercept the cells. The volume of the intercepted cells embedded in the flow pores is less than half the cell volume. Under relatively small shear forces, they can detach from the flow pores and continue flowing forward under the propulsion of the feed liquid, thus maintaining the flow pores in a flowing state. This facilitates the rapid retention of metabolites and other substances. The outflow rate is beneficial for the effective conduct of cell culture. If the SEM pore size of the flow-through well is large, the volume of cells entering the well will also be large. In this case, the cells may either be unable to detach from the well, causing blockage, or the shear force required to detach them will be large. Larger shear force will cause greater damage to the cells, easily forming more cell debris. Cell debris will block the flow-through wells in the groove-like pores, and the outflow rate of metabolites will be very slow, making cell culture ineffective and ultimately failing to obtain high concentrations and high viability of cells.
[0014] Fourth, the complete bubble point reflects the overall pore size characteristics of the microfiltration membrane. The smaller the complete bubble point, the larger the overall pore size of the microfiltration membrane. By controlling the IPA complete bubble point of the microfiltration membrane to 8psi-20psi, the complete bubble point of this invention is relatively small, and the corresponding overall pore size of the microfiltration membrane is relatively large. It has a relatively wide flow path, that is, the pore size of the first surface of the microfiltration membrane is also large. With the synergistic effect of the SEM pore size of the flow pore not being greater than 5μm, the flow pore has a relatively large pore size. When metabolites enter the interior of the microfiltration membrane from the first surface and then flow out through the second surface, there is a wide passage, that is, the metabolites can be discharged quickly. With the synergistic effect of the groove-like pores and the SEM pore size of the flow pore, the metabolites can be discharged quickly and continuously, which is conducive to the continuous and effective perfusion culture.
[0015] In summary, under the synergistic effect of the following: the microfiltration membrane is prepared from polysulfone compounds; the first surface consists of grooved pores and supporting fibers; the average SEM diameter of the supporting fibers is 8 μm-25 μm; the ratio of the average SEM diameter of the supporting fibers to the average SEM minor axis of the grooved pores is 0.55-0.85; the SEM pore size of the flow pores within the grooved pores is no greater than 5 μm; the length direction of the supporting fibers is perpendicular to the length direction of the membrane; and the complete bubble point of the IPA of the microfiltration membrane is 8 psi-20 psi, regardless of whether cells are adsorbed on the supporting fibers or within the grooved pores... In the flow pores, only a small shear force is required to return the cells to the feed solution. The small shear force also causes less damage to the cells. The cells are less likely to form a filter cake layer on the first surface, so the flow pores in the groove-like holes of the first surface are in a flow state. Metabolites are continuously and relatively quickly discharged, resulting in less residual metabolites in the culture system, which is conducive to cell growth. At the same time, the first surface has good pressure resistance, which allows perfusion culture to continue. Therefore, the hollow fiber microfiltration membrane obtained by this invention can be used for perfusion culture, and the obtained cell density and viability are high.
[0016] The aforementioned "several flow holes" refers to two or more flow holes.
[0017] During the membrane preparation process, in the direction perpendicular to the membrane thickness (the membrane of this invention is a hollow fiber membrane, which is perpendicular to the radial direction), its various characteristics, such as pore size and fiber thickness, are roughly uniform and basically consistent. Therefore, a portion of the corresponding plane can be used as the measurement object.
[0018] The groove-like pores refer to the fibers supported on the first surface (such as...). Figure 1 The holes (circled by the blue lines) are concave relative to the supporting fibers, as shown in the image. Figure 1As circled in red, the SEM minor axis of the groove-like pores refers to the distance between lines X1 and X2. Line X1 is a straight line perpendicular to the length of the membrane and intersects the edge of the groove-like pore at only one point. Line X2 is another straight line perpendicular to the length of the membrane and intersects the edge of the groove-like pore at only one point (lines X1 and X2 are located on opposite sides of the groove-like pore). The specific measurement method is as follows: Select a certain area of the SEM image of the first surface (enough to measure the minor axis of the groove-like pores), for example, 1,000,000 μm. 2 (1000μm*1000μm), 250000μm 2 (500μm*500μm), the specific area size depends on the actual situation. Then, use appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually measure the distance between line X1 and line X2, which is the minor axis of the groove-shaped hole. Preferably, measure the minor axis of more than 10 groove-shaped holes and calculate the average value, which is the SEM average minor axis of the groove-shaped hole.
[0019] The SEM diameter of the supporting fibers refers to the distance of the supporting fibers along the length of the membrane in the electron microscope image. It can be measured as follows: Select a certain area of the first surface electron microscope image (any area sufficient to measure the SEM diameter of the supporting fibers), for example, 1,000,000 μm. 2 (1000μm*1000μm), 250000μm 2 (500μm*500μm), the specific area size depends on the actual situation. Then, use appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually measure the diameter of the supporting fiber. Preferably, measure the diameter of the supporting fiber at more than 10 different locations and calculate the average value, which is the SEM average diameter of the supporting fiber. If the diameter of a single supporting fiber is inconsistent, the diameter of multiple locations of a single supporting fiber can be measured and the average value can be taken as the diameter of the single supporting fiber.
[0020] The SEM pore size of the flow-through pores is no greater than 5 μm, meaning that the effective pore size of more than 98% (the percentage of flow-through pores) is no greater than 5 μm. The effective pore size is the smallest membrane pore observable in the SEM image of the first surface after being cut by fibers deeper into the membrane. The minor axis of this pore is the SEM pore size of the flow-through pore, which can be measured as follows: Select a certain area of the SEM image of the first surface (enough to measure the minor axis of the flow-through pore), for example, 2500 μm. 2(50μm*50μm), the specific area size depends on the actual situation. Then, using appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually, the longest line segment among the two points on the outer periphery connecting the flow hole is measured as the major axis. Then, the longest line segment among the two points on the outer periphery of the connecting hole that intersect the major axis perpendicularly is measured as the SEM average aperture of the flow hole. During the measurement process, the flow hole with the larger aperture observed by the naked eye is selected as the measurement object. Of course, those skilled in the art can also obtain the above parameters through other measurement methods. The above measurement methods are for reference only.
[0021] The length direction of the supporting fiber is perpendicular to the length direction of the membrane, meaning that the acute angle between the length direction of the supporting fiber and the length direction of the membrane is greater than 80°. The length direction of the supporting fiber is calculated as follows: select the endpoint A1 on one long side (the first long side) of the supporting fiber, and obtain the point B1 on the other long side (the second long side) that is closest to endpoint A1, thus obtaining the midpoint C1 of line segment A1B1; using the same method, select the other endpoint A2 on the first long side of the supporting fiber, and obtain the point B2 on the second long side that is closest to endpoint A2, thus obtaining the midpoint C2 of line segment A2B2; the acute angle formed by line segment C1C2 and the length direction of the membrane is the angle between the length direction of the supporting fiber and the length direction of the membrane.
[0022] The test methods for the complete bubble point are well known in the art, and the procedures for these tests are explained in detail, for example, in ASTM F316-03 (2019), which is incorporated herein by reference. The complete bubble point of the microfiltration membrane IPA is determined using a 60% isopropanol aqueous solution as the test medium. The pressure at which the microfiltration membrane begins to bubble continuously is read as the complete bubble point of the IPA.
[0023] As a further improvement of the present invention, the initial water contact angle of the first surface is 55°-80°; and the initial water contact angle of the second surface is 65°-88°.
[0024] When the hollow fiber microfiltration membrane of the present invention is used for N-stage perfusion, since cell culture and protein expression are carried out simultaneously in the later stage of perfusion culture, that is, the feed solution includes cells, proteins, metabolites, nutrient solution and other substances, the cells are trapped on the first surface of the hollow fiber microfiltration membrane, while the proteins, metabolites, nutrient solution and other substances pass through the first surface of the hollow fiber microfiltration membrane, then through the membrane wall, and finally through the second surface of the hollow fiber microfiltration membrane, and the proteins are harvested through the permeation end. If the hollow fiber microfiltration membrane has poor hydrophilicity, proteins easily adsorb onto it, forming a filter cake layer that clogs the pores. This slows down or even prevents the excretion of metabolites, making continuous perfusion culture impossible and hindering the acquisition of high-density cells. Simultaneously, protein retention is also high. Therefore, based on a specific pore structure on the first surface, we further control the initial water contact angle of the first surface to be 55°-80°, and the initial water contact angle of the second surface to be 65°-88°. This means both the first and second surfaces of the hollow fiber microfiltration membrane are relatively hydrophilic. Furthermore, since the hollow fiber microfiltration membrane is integrally molded, under the premise that both the first and second surfaces are relatively hydrophilic, the hollow fiber microfiltration... The membrane as a whole is relatively hydrophilic. When proteins in the feed solution pass through the hollow fiber microfiltration membrane, the membrane adsorbs less protein. Because the pore size of the grooved pores is relatively large, and the overall pore size of the hollow fiber microfiltration membrane is also relatively large, both much larger than the size of the protein, the resistance encountered by the protein when passing through the first surface and the entire membrane wall is also relatively small, which helps to reduce the protein rejection rate. That is, under the synergistic effect of the initial water contact angle of the first surface, the initial water contact angle of the second surface, the size of the pores in the grooved pores of the first surface, and the complete bubble point of the microfiltration membrane IPA, the protein rejection rate is low. Consequently, there is less blockage in the hollow fiber microfiltration membrane pathway, allowing metabolites to be continuously discharged, and perfusion culture can be carried out effectively.
[0025] Because the first surface has good hydrophilicity, the supporting fibers adsorb less protein. Even if a small amount is adsorbed, it can return to the feed solution under relatively small shear forces. The protein returning to the feed solution passes through the flow holes, sequentially through the membrane wall of the hollow fiber microfiltration membrane, and then through the second surface before being harvested. This means that the opportunity for "contact" and "anchoring" between the protein and the supporting fibers is reduced from the source, decreasing the formation of a filter cake layer on the supporting fibers. Furthermore, the good hydrophilicity of the first surface, combined with the synergistic effect of the supporting fibers' length direction being perpendicular to the membrane's length direction, further weakens the binding force between the cells and the first surface. This allows the cells to return to the feed solution under even smaller shear forces, resulting in more efficient cell recovery. The difficulty in "growing" on the first surface of a hollow fiber microfiltration membrane indicates that when the first surface has good hydrophilicity, the chance of both proteins and cells forming a filter cake layer is greatly reduced from the source. The shear force required for proteins and cells to peel off on the first surface is smaller. During perfusion culture, the smaller shear force causes less damage to cells and proteins, and there are fewer cell fragments in the feed solution, resulting in less clogging of the membrane pores. Combined with the lower protein retention rate leading to less pore clogging, the flux of the microfiltration membrane decreases less during perfusion culture, which is conducive to the continuous removal of metabolites, making the cell culture process smoother, forming a better virtuous cycle, and promoting the improvement of cell density and viability.
[0026] When hollow fiber microfiltration membranes with good hydrophilicity on the first surface are used for N-1 stage perfusion, the binding force between cells and supporting fibers is also weaker. Therefore, only a smaller shear force is needed to flush the cells back into the feed solution. This reduces the formation of filter cake layer at the source. At the same time, the smaller shear force causes less damage to the cells, and there are fewer cell debris in the feed solution. The cell debris causes less blockage of the membrane pores. In other words, the flux of the microfiltration membrane decreases less during perfusion culture, which is conducive to the continuous removal of metabolites, making the cell culture process smoother and improving cell density and viability.
[0027] Furthermore, the study found that if the initial water contact angle of the first surface is too small, problems such as increased additive precipitation may occur, which may actually reduce cell density and cell viability.
[0028] The initial water contact angle of the first surface and the initial water contact angle of the second surface are tested using the same method. Water is used as the test liquid and a contact angle tester is used. When 10-100 μL of water is evenly dropped onto the test sample surface (the first surface and the second surface in this invention, respectively) for an instant (within 0.4s), a regular contact angle is formed. Multiple tests are conducted, and the average value is taken. Of course, those skilled in the art can also obtain the above parameters through other testing methods. The above testing methods are for reference only.
[0029] As a further improvement of the present invention, the ratio of the average major axis of the groove-shaped pores to the average minor axis of the groove-shaped pores in SEM is 1.5-3.5; the major axis direction of the groove-shaped pores is perpendicular to the length direction of the membrane; and the average major axis of the groove-shaped pores in SEM is 25μm-80μm.
[0030] As a further improvement of the present invention, the average short diameter of the groove-shaped pores in SEM is 15μm-25μm.
[0031] The flow pores within the grooved pores on the first surface of the hollow fiber microfiltration membrane of this invention serve as "entrances" for metabolites and other substances to pass through. The more "entrances," the more channels are available for metabolites, which facilitates increased metabolite excretion. Therefore, by controlling the SEM average major axis of the grooved pores to be 25μm-80μm, the pore diameter of the grooved pores is relatively long. Furthermore, by controlling the ratio of the SEM average major axis to the SEM average minor axis of the grooved pores to be 1.5-3.5, the corresponding surface perimeter of a single grooved pore (the perimeter of the opening portion on the first surface) is also relatively large. The larger the perimeter of the surface, the larger the surface area of the individual groove-like pores, resulting in more channels for the flow pores to form and more channels for metabolites to enter. Combined with the synergistic effect of the microfiltration membrane's IPA bubble point of 8-20 psi and the SEM pore size of the flow pores being no greater than 5 μm, which results in relatively large pore sizes, the channels for metabolite discharge are wide and numerous. Simultaneously, the larger the surface perimeter of each individual groove-like pore, the lower the resistance to metabolites entering the groove-like pores. Therefore, when the hollow fiber microfiltration membrane of this invention is used for perfusion culture, the resistance to metabolites entering the groove-like pores is relatively small, and further... The wider and more numerous flow paths, coupled with lower resistance to metabolites entering the grooved pores, result in a smaller transmembrane pressure gradient. This leads to a slower compaction rate of cells and proteins adsorbed on the first surface, allowing them to return to the feed solution under shear force before they can be compacted. The lower shear force also reduces damage to cells and proteins, resulting in less cell debris and slower pore blockage. Overall, the rate of metabolite removal is improved, and the amount of residual metabolites in the feed solution is reduced, allowing for more efficient perfusion culture. Furthermore, even with relatively large grooved pores, the compressive strength of the first surface remains relatively high. If the perfusion culture duration can be maintained, higher cell density and viability can be obtained. In addition, less shear force will cause less damage to the protein, which is conducive to improving protein yield. If the average long diameter of the grooved pores in SEM is greater than 80 μm, the supporting effect of the corresponding supporting fibers on the grooved pores is weak, which is not conducive to maintaining the first surface compressive strength, and is not conducive to improving cell density and viability. Similarly, if the average long diameter of the grooved pores in SEM is less than 25 μm, the surface perimeter of the corresponding individual grooved pores is also relatively small, the improvement of metabolite excretion rate is limited, and it is also not conducive to improving cell density and viability.
[0032] The long axis of the grooved pores is perpendicular to the length of the membrane, meaning the long axis of the grooved pores is parallel to the length of the supporting fibers. As mentioned above, the flow path of the liquid on the first surface is a continuous alternation of supporting fiber-grooved pore-supporting fiber-grooved pore. That is, when the liquid passes through the supporting fibers, it travels the distance of the supporting fiber's diameter; when it passes through the grooved pores, it travels the distance of the grooved pore's short axis. Combined with the SEM average diameter of the supporting fibers (8μm-25μm) and the SEM average short axis of the grooved pores (15μm-25μm), the supporting fibers can better support the grooved pores. The pores give the first surface better pressure resistance, and the flow path of the feed solution has a relatively uniform curve shape, resulting in more uniform shear force, less damage to cells, and stable propulsion of the feed solution. The binding force between cells and the first surface is relatively weak, which is conducive to the reduction of the shear force required to remove cells from the first surface. The lower shear force results in less damage to cells and proteins, less cell debris in the feed solution, slower membrane pore blockage, and better maintenance of the excretion rate of metabolites. The lower amount of residual metabolites in the feed solution system is conducive to more effective perfusion culture, and ultimately the cell density and viability are further improved.
[0033] The major axis of the groove-like pores in SEM refers to the distance between lines Y1 and Y2. Line Y1 is a line parallel to the length of the membrane and intersects the edge of the groove-like pore at only one point. Line Y2 is another line parallel to the length of the membrane and intersects the edge of the groove-like pore at only one point (lines Y1 and Y2 are located on opposite sides of the groove-like pore). The specific measurement method is as follows: Select a certain area of the SEM image of the first surface (enough to measure the major axis of the groove-like pores), for example, 1,000,000 μm. 2 (1000μm*1000μm), 250000μm 2 (500μm*500μm), the specific area size depends on the actual situation. Then, use appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually measure the distance between line Y1 and line Y2, which is the major diameter of the groove-shaped hole. Preferably, measure the major diameter of more than 10 groove-shaped holes and calculate the average value, which is the SEM average major diameter of the groove-shaped hole.
[0034] As a further improvement of the present invention, the groove-like pores further include flow fibers for forming flow pores, the SEM average diameter of the flow fibers being 0.1μm-0.3μm; and the porosity of the microfiltration membrane being 60%-80%.
[0035] As mentioned above, we know that the pore size of the flow-through pores is relatively large. Therefore, we further adjusted the SEM average diameter of the flow-through fibers to 0.1μm-0.3μm. A slightly coarser diameter allows for better support of the larger pore size, ensuring the flow-through pores remain intact during perfusion culture. This allows for the continuous and rapid removal of metabolites, keeping residual metabolites in the solution low and enabling sustained and effective perfusion culture. Simultaneously, the synergistic effect with the supporting fibers helps maintain the integrity of the grooved pores, resulting in better compressive strength on the first surface. This allows for longer perfusion culture times, promoting increased cell density and viability, and reducing protein retention. While a larger SEM average diameter of the flow-through fibers would better support the pores, it would also occupy more area of the grooved pores, affecting the flow-through pore size. The reduced surface area actually hinders the rate of metabolite excretion. If the average SEM diameter of the flow fibers is small, although the area of the flow pores within the corresponding grooves is greater, the thinner flow fibers are at risk of breaking under shear force. Broken fibers connect adjacent membrane pores, increasing the risk of cells completely entering the connected pores. Consequently, the membrane pores lose their flow capacity, which is detrimental to the rate of metabolite excretion. Even if cells do not completely enter the connected pores, the volume of cells embedded within them is relatively large, requiring greater shear force to detach them. This greater shear force damages cells and proteins, increasing cell debris and leading to pore blockage, which also hinders the rate of metabolite excretion. In short, whether the diameter of the flow fibers is too large or too small, it is not conducive to obtaining higher cell density and viability.
[0036] Porosity reflects the volume ratio of pores in a hollow fiber microfiltration membrane. The higher the porosity, the larger the volume ratio of pores in the overall membrane, and the more flow paths the fluid can pass through. The hollow fiber microfiltration membrane of this invention has a porosity of 60%-80%, which is relatively high, resulting in a large number of flow paths. Combined with the IPA bubble point of 8psi-20psi, the overall pore size of the microfiltration membrane is relatively large, meaning that the hollow fiber microfiltration membrane has wide and numerous flow paths, resulting in faster metabolite removal and more effective perfusion culture. At the same time, the high porosity structure gives the hollow fiber microfiltration membrane itself a large contaminant holding capacity. Even if a small amount of cell debris or other particles are trapped inside the hollow fiber microfiltration membrane, it still has many flow paths, maintaining a high rate of metabolite removal and allowing perfusion culture to proceed at a relatively fast speed. In addition, at this porosity, the overall mechanical strength of the microfiltration membrane is also good, allowing perfusion culture to continue for a longer period of time, increasing cell density and viability, and reducing protein retention.
[0037] The average diameter of the flowing fiber was determined by selecting a specific area (e.g., 2500 μm) from the electron micrograph of the first surface (enough to measure the diameter of the flowing fiber). 2 (50μm*50μm), 900μm 2 (30μm*30μm), the specific area size depends on the actual situation. Then, use appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually measure the diameter of the flow fiber. Preferably, measure the diameter of more than 10 flow fibers and calculate the average value, which is the SEM average diameter of the flow fiber.
[0038] Commonly used methods for testing porosity include mercury intrusion porosimetry, density method, and wet-dry film weighing method. Of course, those skilled in the art can also obtain the above parameters through other testing methods. The above testing methods are for reference only.
[0039] As a further improvement of the present invention, the supporting fiber includes a plurality of flow guide holes, the SEM average short diameter of the flow guide holes being 1μm-3μm; the ratio of the SEM average major diameter of the flow guide holes to the SEM average short diameter of the flow guide holes being 2-3.
[0040] The more pores on the first surface, the more channels for metabolites to enter. Therefore, by controlling the supporting fibers to contain several flow-guiding pores, we can provide more outflow pathways for metabolites, resulting in less residual metabolites in the feed system. This allows for more efficient perfusion culture, leading to higher cell density. The presence of flow-guiding pores can disperse the feed flowing through the supporting fibers, reducing concentration polarization and thus lowering the shear force at the first surface, which is beneficial for improving cell viability and reducing protein retention.
[0041] Furthermore, by controlling the SEM short axis of the flow-through holes to 1μm-3μm, which is extremely small relative to the size of the cells, the volume of cells embedded inside the flow-through holes is minimal when cells pass through them. The required shear force is also minimal, easily separating the cells from the flow-through holes. In other words, the overall shear force required to separate cells from the first surface does not increase. However, flow-through holes within this range effectively increase the discharge rate of metabolites, resulting in less residual metabolites in the solution, more efficient perfusion culture, and further improvement in cell density. Simultaneously, the SEM short axis of the flow-through holes within this range is extremely large relative to the size of protein molecules, resulting in less resistance to protein passage and a lower protein retention rate. Since the support fibers are relatively wide, setting 1μm-3μm flow-through holes on the support fibers has minimal impact on their strength. The support fibers can still effectively support the grooved pores, and the first surface still possesses acceptable compressive strength, allowing the perfusion culture time to be maintained.
[0042] Furthermore, by controlling the ratio of the SEM average major axis to the SEM average minor axis of the flow guide hole to 2-3, the major axis of the flow guide hole is slightly longer than the minor axis. While this has a relatively small impact on the compressive strength of the first surface, the edges of the flow guide hole can serve as entry points for removing adsorbed cells or proteins. Through the synergistic effect of the SEM minor axis of the flow guide hole and the ratio of its SEM average major axis to the SEM average minor axis, the flow guide hole achieves a relatively large perimeter. A larger perimeter provides more entry points to "pry" the adsorbed cells or proteins, thus facilitating the removal of adsorbed cells or proteins from the first surface. With a smaller shear force, the shear force required for cells or proteins to detach from the supporting fibers is smaller. The smaller the shear force, the less damage to cells and proteins, resulting in higher cell viability. Under a smaller shear force, cells or proteins can return to the feed solution, and the drainage holes can remain in a flowing state. At the same time, these drainage holes on the supporting fibers have a wider flow path than circular holes, allowing metabolites to be discharged continuously and more quickly. There are fewer residual metabolites in the feed solution, which is conducive to more effective perfusion culture, obtaining higher cell density, and reducing protein retention rate.
[0043] The aforementioned "several guide holes" refers to two or more guide holes.
[0044] The SEM average major and minor axes of the flow guide holes can be measured using the following method: Select a certain area of the SEM image of the first surface (enough to measure the major and minor axes of the flow guide holes), for example, 2500 μm. 2 (50μm*50μm), the specific area size depends on the actual situation. Then, use appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually measure the longest line segment among the two points on the outer periphery of the connecting hole as the major diameter, and measure the longest line segment among the two points on the outer periphery of the connecting hole that intersects the major diameter perpendicularly as the SEM average minor diameter of the connecting hole. Take the average value of multiple measurements (preferably more than 10 measurements) to obtain the SEM average major diameter and SEM average minor diameter of the connecting hole.
[0045] As a further improvement of the present invention, the area ratio of the flow guide hole is 5%-15%; the area ratio of the groove-shaped hole is 40%-65%.
[0046] Furthermore, by controlling the pore area ratio of the grooved pores to 40%-65%, the area ratio of the grooved pores is relatively large, resulting in a larger surface area of the grooved pores and a greater number of flow pores that can be formed. This provides more channels for metabolites to enter. Combined with the synergistic effect of the microfiltration membrane's IPA bubble point of 8-20 psi and the SEM pore size of the flow pores being no larger than 5 μm, which results in relatively large pore sizes, the channels for metabolites and proteins to exit are numerous and wide. The less residual metabolites in the feed solution, the more effective the perfusion culture, which is conducive to increasing cell density and reducing protein retention. Furthermore, the average SEM length of the grooved pores... Due to the synergistic effect of the ratio of the SEM average major diameter to the SEM average minor diameter of the grooved pores, the grooved pores on the first surface are larger and more numerous, and the total surface perimeter of the grooved pores is also larger. This results in less resistance to metabolites entering the flow pores, a smaller transmembrane pressure gradient, a slower compaction rate of cells and proteins adsorbed on the first surface, less shear force required to peel cells and proteins off the first surface, and less damage to cells and proteins, ultimately leading to higher cell viability. At the same time, with the support of the supporting fibers, the larger pore area ratio of the grooved pores ensures that the first surface still has good compressive strength, allowing the perfusion culture time to be maintained better.
[0047] Since the first surface is composed of grooved pores and supporting fibers, when the pore area ratio of the grooved pores is 40%-65%, the corresponding area ratio of the supporting fibers is 35%-60%. Further controlling the pore area ratio of the guide holes to 5%-15%, the proportion of the guide holes is moderately small. Combined with the synergistic effect of the ratio of the short diameter of the guide holes to the long diameter of the guide holes, the impact on the compressive strength of the first surface is small, which allows the perfusion culture time to be maintained. However, these small and slightly more guide holes result in higher cell density, higher cell viability, and lower protein retention rate obtained from perfusion culture.
[0048] The porosity of the guide holes refers to the ratio of the sum of the areas of all guide holes on the supporting fiber to the area of the first surface. It is measured using ImageJ, as detailed below:
[0049] ① Open the image; Open the image (in this invention, it refers to the electron microscope image of the first surface, preferably an electron microscope image that can clearly show the flow guide hole) in the image processing software ImageJ. File>Open, select the electron microscope image and click Open;
[0050] ② Set the scale; Use the line tool from the toolbar to draw a straight line within the scale area, making the drawn line the same length as the scale on the electron microscope image. Select Analyze > Set Scale, enter the length of the scale in "KnownDistance" (for example, enter 10), enter the unit in "Unitoflength" (for example, enter um), and select OK.
[0051] ③ Set measurement parameters; In Analyze>SetMeasurements, ensure that “Area” is checked, and then select OK;
[0052] ④ Select and measure the membrane pores; Use FreehandSelection from the toolbar to select the membrane pores. After selection, select Analyze > Tools > ROIManager. In the pop-up task box, click "Add". Repeat the above operation until all the flow guides in the electron microscope image are selected. Use the Shift key to select all the added data in the task box, click "Measure", and sum the results and divide by the area of the electron microscope image to get the pore area ratio of the flow guides.
[0053] The pore area ratio of grooved pores refers to the ratio of the sum of the areas of the projections of the grooved pores onto the first surface to the area of the first surface. The test method is the same as that of the pore area ratio of the guide hole, except that the membrane pores selected in step ④ are grooved pores.
[0054] As a further improvement of the present invention, the ratio of the initial bubble point of the IPA of the microfiltration membrane to the complete bubble point of the IPA of the microfiltration membrane is 0.85-0.95; the thickness of the microfiltration membrane is 110μm-200μm.
[0055] The initial bubble point (IPA) of a microfiltration membrane reflects its maximum pore size. The ratio of the initial bubble point to the complete bubble point (IPA) of the microfiltration membrane is 0.85-0.95, which is close to 1. This indicates a relatively uniform overall pore size distribution, resulting in a stable fluid velocity and lower shear force generated by the fluid, thus reducing protein damage and retention. It also minimizes damage to cells in the feed solution, producing less cell debris and maintaining better flow path. Because the microfiltration membrane of this invention has a relatively large pore size, the rate of metabolite removal can be maintained at a high speed, allowing for more effective perfusion culture and achieving higher cell density and viability. Furthermore, in conjunction with porosity, the microfiltration membrane has numerous and wide flow paths, allowing for better removal of metabolites and proteins, further increasing cell concentration and reducing protein retention.
[0056] Furthermore, by adjusting the thickness of the microfiltration membrane to 110μm-200μm, we achieved a relatively thick membrane, which is beneficial for the continuous perfusion culture. Simultaneously, through the synergistic effect of the complete bubble point of IPA in the microfiltration membrane and the ratio of the initial bubble point of IPA to the complete bubble point of IPA in the microfiltration membrane, the microfiltration membrane as a whole has a relatively wide flow path. When used for N-stage perfusion, proteins can pass through quickly without traveling an excessively long distance, which is beneficial for reducing the protein retention rate.
[0057] The test method for the initial bubble point of the microfiltration membrane IPA is similar to the test method for the complete bubble point of the IPA, the difference being that the pressure at which the microfiltration membrane begins to bubble is read.
[0058] The thickness of the microfiltration membrane is measured by measuring the distance between the first and second surfaces on a cross-sectional electron microscope image of the membrane using computer software (such as Matlab, NIS-Elements, etc.) or manually.
[0059] As a further improvement of the present invention, the SEM pore size of the microfiltration membrane first increases and then decreases in the thickness direction from the first surface to the second surface; the region where the SEM pore size first increases is a reinforcing layer on the side closer to the first surface, and the thickness of the reinforcing layer is 5μm-25μm; the reinforcing layer also includes reinforcing fibers for forming pores in the reinforcing layer, and the SEM average diameter of the reinforcing fibers is 0.15μm-0.6μm.
[0060] In this invention, the SEM pore size of the microfiltration membrane increases and then decreases along the thickness direction from the first surface to the second surface. Metabolites and proteins first pass through the expansion channels, resulting in lower mass transfer resistance and less protein adsorption in the expansion channel region, further reducing protein retention. The lower mass transfer resistance allows fluid to pass through the pores of the first surface into the interior of the microfiltration membrane under a lower transmembrane pressure difference. The lower transmembrane pressure difference also reduces the overall compression effect on the microfiltration membrane and discourages the formation of a robust filter cake layer on the first surface. Substances adsorbed on the first surface (e.g., cells or proteins) can return to the feed solution under less shear force. Both the lower transmembrane pressure difference and shear force contribute to the microfiltration membrane's ability to form a robust filter cake layer. The longer lifespan of the filter membrane allows for longer perfusion culture, while the lower shear force results in less damage to cells and proteins, improving cell viability and protein yield. Furthermore, the reduced shear force leads to less cell debris, enabling more efficient cell culture. Additionally, the lower mass transfer resistance and faster flow of metabolites and other fluids through the region with increasing pore size, followed by a region with decreasing pore size where micro-turbulence promotes fluid flow towards the second surface, results in a faster overall fluid velocity across the membrane cross-section. This allows for quicker removal of metabolites, reducing residual metabolites in the feed solution and further facilitating cell culture. Ultimately, this leads to improved cell density and viability.
[0061] To meet the requirements of longer perfusion culture, we added a reinforcement layer near the first surface. By controlling the thickness of the reinforcement layer to 5μm-25μm and the average SEM diameter of the reinforcement fibers to 0.15μm-0.6μm, the reinforcement layer is relatively thick and the reinforcement fibers are relatively coarse. The reinforcement layer itself has high strength, which can better support the structure of the first surface, giving the first surface better compressive strength. This allows the perfusion culture to be used for a longer period of time, ultimately obtaining a higher density of cells.
[0062] One plane of the reinforcing layer is designated as the first surface. The position of the other plane is determined using a scanning electron microscope (SEM) in this invention to characterize the overall cross-section of the membrane. For example, an SEM image of the membrane cross-section near the first surface with a magnification of 1000 or 2000 is obtained. Then, the fiber diameters of different planes in the SEM image of the membrane cross-section are measured sequentially. This is done by measuring the SEM diameters of multiple fibers on the same plane and calculating the average value to obtain the average SEM diameter of fibers on different planes. When the average SEM diameter of a fiber on a certain plane is significantly different from the average SEM diameter of an adjacent fiber on a plane farther from the first surface... When the diameter ratio is less than 0.7, the plane (hereinafter referred to as plane P1) is the other plane of the reinforcing layer. The area between the first surface and plane P1 is the reinforcing layer, and the distance between the first surface and plane P1 is the thickness of the reinforcing layer. This thickness is measured by computer software (such as Matlab, NIS-Elements, etc.) or manually on a cross-sectional electron microscope image of the membrane. The average diameter of the reinforcing fiber in the SEM is measured by a certain area of the cross-sectional electron microscope image (any area sufficient to measure the diameter of the reinforcing fiber), for example, 1600 μm. 2 (40μm*40μm), 400μm 2 (20μm*20μm), the specific area size depends on the actual situation. Then, use appropriate computer software (such as Matlab, NIS-Elements, etc.) or manually measure the diameter of the reinforcing fiber. Preferably, measure the diameter of the reinforcing fiber on more than 10 different planes and calculate the average value, which is the SEM average diameter of the reinforcing fiber.
[0063] As a further improvement of the present invention, the pore area ratio of the second surface is 25%-55%; the SEM average pore diameter of the pores on the second surface is 0.3μm-1μm.
[0064] The pores on the second surface are the final exit points for metabolites and proteins. Due to the relatively small size (average SEM pore size 0.3μm-1μm) and numerous pores (pore area ratio 25%-55%) on the second surface, the mass transfer resistance of metabolites and proteins passing through these pores is low. Combined with the synergistic effect of the flow pores within the grooved pores of the first surface (SEM pore size no greater than 5μm) and the IPA bubble point of the microfiltration membrane being 8psi-20psi, the mass transfer resistance of metabolites and proteins through the microfiltration membrane is low, resulting in faster passage of metabolites and proteins and greater protein adsorption within the microfiltration membrane. Less protein retention and fewer metabolite residues in the feed solution allow for faster perfusion culture. Lower mass transfer resistance requires less transmembrane pressure, which in turn reduces pressure on the microfiltration membrane, extending its lifespan and allowing for longer perfusion culture sessions, ultimately resulting in higher cell density. The smaller transmembrane pressure also slows down the compaction of cells and proteins adsorbed on the first surface, reducing the shear force required for cells and proteins to detach from the first surface. This reduced shear force causes less damage to cells and proteins, ultimately improving cell viability and protein yield.
[0065] The porosity of the second surface refers to the ratio of the sum of the areas of all pores on the second surface to the total area of the second surface. It can be measured using ImageJ. Specifically,
[0066] ① Image opening and pixel adjustment: Open the electron microscope image of the second surface in the image processing software ImageJ. File>Open, select the electron microscope image and click Open, then select Image>Type>8-bit to convert the image to an 8-bit grayscale image;
[0067] ② Measure the porosity of the second surface: In Image>Adjust>Threshold, adjust the scale in the dialog box that appears so that all the membrane pores are filled. The percentage obtained is the porosity of the second surface. Select at least 5 electron micrographs of different second surfaces as the measurement objects and take the average value.
[0068] The SEM average aperture diameter of the holes on the second surface refers to the equivalent aperture diameter of the holes on the second surface (i.e., the diameter of a circle with the same SEM average area as the holes on the second surface). The specific measurement method is as follows:
[0069] ① Open the image; Open the image (in this invention, it refers to the electron microscope image of the second surface, such as an electron microscope image with a magnification of 5000) in the image processing software ImageJ. File>Open, select the electron microscope image and click Open;
[0070] ② Set the scale; Use the line tool from the toolbar to draw a straight line within the scale area, making the drawn line the same length as the scale on the electron microscope image. Select Analyze > Set Scale, enter the length of the scale in "KnownDistance" (for example, enter 10), enter the unit in "Unitoflength" (for example, enter um), and select OK.
[0071] ③ Set measurement parameters; In Analyze>SetMeasurements, ensure that “Area” is checked, and then select OK;
[0072] ④ Select and measure the membrane pores; Use FreehandSelection from the toolbar to select the membrane pores. After selecting, select Analyze > Tools > ROIManager. In the pop-up task box, click "Add". Repeat the above operation. It is preferable to select more than 10 membrane pores. Use the Shift key to select all the added data in the task box, click "Measure", calculate the average area of the pores on the selected second surface, and then calculate the radius length r using the formula S (average area of membrane pores) = πr². 2r is the equivalent pore diameter of the pores on the second surface.
[0073] As a further improvement of the present invention, the cell density obtained when the microfiltration membrane is used for cell perfusion culture is not less than 3*102 7 The cell count / mL is not less than 90%; the tensile strength of the microfiltration membrane is not less than 3.5 MPa; and the water flux of the microfiltration membrane is not less than 700 LMH / psi.
[0074] Cell density refers to the number of cells per unit volume in the feed solution. It is an important parameter in perfusion culture. Higher cell density indicates better cell growth, which is beneficial for improving protein synthesis capacity per unit volume and increasing protein titer. When the hollow fiber microfiltration membrane of this invention is used for perfusion culture, its cell density can reach no less than 3*102. 7 It has cells / mL and a good cell density.
[0075] Cell viability refers to the proportion of live cells. The higher the cell viability, the fewer apoptotic cells occur during perfusion culture. When the hollow fiber microfiltration membrane of this invention is used for perfusion culture, its cell viability is not less than 90%, which is a good cell viability, and relatively few cells undergo apoptosis during the culture process.
[0076] Mechanical strength tests showed that the hollow fiber microfiltration membrane prepared by this invention has a tensile strength of not less than 3.5 MPa, exhibiting excellent mechanical properties, which is beneficial for the continuous perfusion culture.
[0077] The sample was stretched at a constant speed (50 mm / min, 30 mm between the upper and lower clamps) using a tensile testing machine at room temperature until it broke, and the tensile strength was measured. This process was repeated 3 times and the average value was taken as the final tensile strength.
[0078] Permeation flux, also known as permeation rate or simply flux, refers to the amount of substance that passes through a unit area of membrane per unit time under a certain operating pressure in a hollow fiber microfiltration membrane. The magnitude of flux reflects the rate at which metabolites are expelled; a higher flux indicates a faster rate of metabolite expulsion. The polysulfone-based hollow fiber microfiltration membrane of this invention has a water flux of no less than 700 LMH / psi, exhibiting a high water flux. This indicates that when the hollow fiber microfiltration membrane is used for perfusion culture, the rate of metabolite expulsion is relatively fast. Metabolites can pass through the hollow fiber microfiltration membrane quickly, allowing for continuous perfusion culture, which is beneficial for obtaining high-density cells and offers significant economic benefits.
[0079] For the test method of water flux of hollow fiber microfiltration membrane, please refer to paragraphs 0150-0153 of the specification of patent CN119607899A.
[0080] A second aspect of the present invention provides a method for preparing a polysulfone-based hollow fiber microfiltration membrane as described above, comprising the following steps:
[0081] Step 1: Preparation of casting solution and core solution:
[0082] The casting solution is composed of a sulfone polymer, a first organic solvent, and a first porogen, wherein the sulfone polymer has a mass content of 15%-20%, and the first porogen has a mass content of 5%-8%.
[0083] The core fluid is composed of fatty alcohol, a second organic solvent, and an inorganic salt, wherein the mass content of the second organic solvent is 60%-80%, and the mass content of the inorganic salt is 0.5%-2%.
[0084] The first porogen is selected from at least one of PVPK90 and PVPK120;
[0085] The weight-average molecular weight of the sulfone polymer is 140,000 to 200,000.
[0086] The fatty alcohol is selected from at least one of isopropanol and ethanol;
[0087] The inorganic salt is selected from at least one of sodium chloride and lithium chloride;
[0088] Step 2: Spinning:
[0089] The casting solution and core solution prepared in step one are extruded together from the spinneret to form a molded product with a first surface and a second surface.
[0090] The extrusion rate of the core liquid is 10 mL / min-15 mL / min, the extrusion rate of the casting liquid is 8 mL / min-10 mL / min, and the extrusion rate of the casting liquid is less than the extrusion rate of the core liquid.
[0091] Step 3: Pre-phase separation:
[0092] The molded product obtained in step two is subjected to pre-phase separation to obtain film I. The pre-phase separation is carried out in an air section with a length of 15cm-40cm. During the pre-phase separation process, a stretching treatment is performed, with a stretching rate of 2%-15%.
[0093] Step 4: Phase Separation
[0094] The biofilm I obtained in step three is immersed in a coagulation bath to completely separate phases and form biofilm II. The coagulation bath is composed of isopropanol and water, and the mass content of isopropanol is 10%-30%.
[0095] Step 5: Cleaning and drying:
[0096] The membrane II obtained in step four was washed with pure water and then dried to obtain a polysulfone hollow fiber microfiltration membrane.
[0097] As a further improvement of the present invention, the casting solution further comprises poloxamer 407, wherein the mass content of poloxamer 407 is 0.5%-2%; the polysulfone substance is at least one of bisphenol A polysulfone, polyethersulfone, and polyphenylsulfone.
[0098] As a further improvement of the present invention, the stretching rate in step two is 5%-12%; the temperature of the casting solution is 40℃-60℃; and the temperature of the core solution is 20℃-30℃.
[0099] As a further improvement of the present invention, the casting solution further comprises a second pore-forming agent, the second pore-forming agent being selected from at least one of PEG200 and PEG400; the mass content of the second pore-forming agent is 6%-10%; the first organic solvent and the second organic solvent are each independently selected from at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0100] As a further improvement of the present invention, the temperature of the coagulation bath is 40℃-70℃; the phase separation time of the film-forming unit (I) in the coagulation bath is 80s-200s; the relative humidity of the air section is 60%-80%, and the temperature is 10℃-20℃.
[0101] In this invention, relative humidity refers to relative humidity at room temperature.
[0102] In preparing the polysulfone-based hollow fiber microfiltration membrane of the present invention, a casting solution is first prepared. The casting solution includes a sulfone polymer as a film-forming substance, a first organic solvent for dissolving the sulfone polymer, and a first pore-forming agent. The sulfone polymer is selected from at least one of bisphenol A polysulfone, polyethersulfone, and polyphenylene sulfone, and its weight-average molecular weight is 140,000-200,000. Sulfone polymers with such a molecular weight have relatively high strength. However, when the weight-average molecular weight of the sulfone polymer is relatively high, the corresponding molecular chains are relatively longer, the degree of chain segment entanglement is relatively higher, and the molecular chain migration speed is relatively slower. Simultaneously, the first pore-forming agent is selected from at least one of PVPK90 and PVPK120. Both PVPK90 and PVPK120 have very high weight-average molecular weights. The first porogen is larger than that of sulfone polymers. The molecular chain of the first porogen moves more slowly than that of sulfone polymers. Under the synergistic effect of inorganic salts in the core liquid, the extrusion rate of the casting liquid in step two being less than that of the core liquid, and the stretching during the pre-phase separation process in step three, the sulfone polymers in the casting liquid near the first surface aggregate to form a sulfone polymer-rich phase (mainly sulfone polymers), and the first porogens also aggregate to form a first porogen-rich phase (mainly the first porogen). Then, under the action of the core liquid, phase separation begins. The sulfone polymer-rich phase forms supporting fibers, and the length direction of the supporting fibers is perpendicular to the length direction of the membrane. The first porogen-rich phase forms groove-like pores under the action of the core liquid. By adjusting the mass composition of the sulfone polymer, the first organic solvent (selected from at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide), and the first pore-forming agent, the casting solution is made to have a suitable viscosity. The viscosity of the casting solution also has a certain influence on the structure and performance of the final hollow fiber microfiltration membrane, such as the pore size of the flow pores. This provides a basis for the first surface of the final hollow fiber microfiltration membrane to consist of grooved pores and supporting fibers. The reasonable diameter of the supporting fibers, the reasonable short diameter of the grooved pores, the reasonable pore size of the flow pores, the direction of the supporting fibers, and the reasonable IPA bubble point of the microfiltration membrane provide a basis for the prepared hollow fiber microfiltration membrane to be effectively used in perfusion culture. Preferably, by controlling the temperature of the casting solution to 40℃-60℃, the shape of the grooved pores (the ratio of the long axis to the short axis) is within a more preferred range.
[0103] The composition of the core liquid primarily affects the structure of the first surface and its vicinity in the hollow fiber microfiltration membrane. The core liquid used in the extrusion of the hollow fiber microfiltration membrane of this invention consists of a fatty alcohol (at least one selected from isopropanol and ethanol), a second organic solvent (at least one selected from dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide), and an inorganic salt (at least one selected from sodium chloride and lithium chloride). When the inorganic salt in the core liquid comes into contact with the casting liquid, the casting liquid in contact with the inorganic salt becomes unstable, causing the casting liquid forming the first surface and its vicinity to move. This is related to the specific weight-average molecular weight sulfone polymer in step one, the specific type of first pore-forming agent, the fact that the extrusion rate of the casting liquid in step two is less than the extrusion rate of the core liquid, and the step three... Under the synergistic effect of the stretching action, the sulfone polymer and the first porogen move along the length of the membrane. Since the phase separation rate of the core liquid to the casting liquid is relatively slow, the first surface has not yet had time to separate phases. The first surface and its surrounding area form a sulfone polymer-rich phase (mainly sulfone polymer) and a first porogen-rich phase (mainly the first porogen), providing a foundation for the formation of grooved pores and supporting fibers on the first surface. Simultaneously, the presence of a small amount of inorganic salt in the core liquid increases its viscosity and slows down the phase separation rate. Under the specific content of inorganic salts, fatty alcohols, and the second organic solvent, and with the synergistic effect of the sulfone polymer content in the casting liquid, the pore size of the flow holes within the grooved pores on the first surface is within a reasonable range. Preferably, by controlling the core liquid temperature to 20℃-30℃, the SEM average minor diameter of the flow holes and the shape of the flow holes (the ratio of the major to minor diameter) are within preferred ranges.
[0104] Preferably, the casting solution further comprises a second pore-forming agent, wherein the second pore-forming agent is selected from at least one of PEG200 and PEG400, that is, the casting solution is composed of a sulfone polymer, a first organic solvent, a first pore-forming agent and a second pore-forming agent. The second pore-forming agent has a small molecular weight and can exist in the rich phase of the sulfone polymer. Under the action of the core liquid, phase separation occurs, mainly forming relatively small flow pores. By controlling the mass content of the second pore-forming agent to 6%-10%, the pore area ratio of the formed flow pores is within the preferred range.
[0105] The second step involves extruding the prepared casting solution and core solution together from the spinneret. The casting solution forms a molded product with a first surface and a second surface in the nozzle, namely a hollow fiber microfiltration membrane. The extruded hollow fiber microfiltration membrane has a first surface facing the inner lumen and a second surface opposite to the lumen. The extrusion rate of the core solution is 10 mL / min-15 mL / min, and the extrusion rate of the casting solution is 8 mL / min-10 mL / min. The extrusion rate of the casting solution is less than that of the core solution. In other words, during the extrusion process, the extrusion rate of the core solution is greater than that of the casting solution. This rate difference generates a continuous and gentle annular shear gradient at the interface of the first surface. The core solution exerts a certain forward drag force on the casting solution near the first surface, which is conducive to the formation of sulfone polymer-rich phase and first pore-forming agent-rich phase, and thus conducive to the formation of groove-like pores with reasonable pore size and support fibers with reasonable width.
[0106] Step three, pre-phase separation, involves pre-separating the molded product obtained in step two to obtain film I. During pre-phase separation, a stretching process is simultaneously performed. During stretching, the polymer molecular chains move along the stretching direction, while the corresponding groove-like pores preferentially expand perpendicular to the stretching direction (i.e., perpendicular to the length of the film). Combined with the weight-average molecular weight of the sulfone polymer in the casting solution, the specific composition of the first pore-forming agent, the presence of inorganic salts in the core solution, and the fact that the extrusion rate of the casting solution is lower than that of the core solution, the resulting support fibers are perpendicular to the length of the film. The length direction of the groove-like pores is perpendicular to the length direction of the membrane. By controlling the stretching rate within the range of 2%-15%, the diameter of the supporting fibers of the prepared hollow fiber microfiltration membrane is within a reasonable range, and the ratio of the diameter of the supporting fibers to the minor diameter of the groove-like pores is also within a reasonable range. Preferably, by controlling the stretching rate to 5%-12%, the major diameter of the prepared groove-like pores is within a preferred range. By controlling the length of the air section, and in conjunction with the phase separation in step four, the prepared hollow fiber microfiltration membrane has a reasonable pore size.
[0107] Step four involves immersing the biofilm I obtained in step three into a coagulation bath to completely separate the phases and form biofilm II. The coagulation bath consists of isopropanol and water, with the mass content of isopropanol being 10%-30%. Under the synergistic effect of the sulfone polymer in the casting solution, which has a mass content of 15%-20%, the hollow fiber microfiltration membrane finally formed has a small range of IPA complete bubble point. As the coagulation bath penetrates into the interior of the microfiltration membrane through the pores formed on the second surface, the amount of coagulation bath entering decreases with distance from the second surface, the phase separation rate slows down, and the resulting membrane pores become larger. This creates a region where the SEM pore size of the microfiltration membrane decreases further along the thickness direction from the first surface to the second surface. Similarly, the core liquid penetrates into the interior of the microfiltration membrane through the pores on the first surface. The amount of core liquid entering decreases with distance from the first surface, the phase separation rate slows down, and the resulting membrane pores become larger. This creates a region where the SEM pore size of the microfiltration membrane first increases with distance from the first surface to the second surface. In other words, under the combined action of the casting solution, core liquid, pre-phase separation, and phase separation, a structure is formed where the SEM pore size of the microfiltration membrane first increases and then decreases with distance from the first surface to the second surface.
[0108] After complete phase separation, the biofilm II was washed with pure water and dried to obtain a polysulfone hollow fiber microfiltration membrane.
[0109] Preferably, the casting solution further contains poloxamer 407. Since poloxamer 407 has hydrophilic polyoxyethylene chains at both ends and has good compatibility with sulfone polymers, by controlling the mass content of poloxamer 407 to be 0.5%-2%, it can be well mixed with sulfone polymers, and the hydrophilic groups can be evenly distributed in all parts of the hollow fiber microfiltration membrane. At the same time, it can also improve the hydrophilicity of the hollow fiber microfiltration membrane and reduce the initial water contact angle of the hollow fiber microfiltration membrane. However, if the mass content of poloxamer 407 is too high, the strength of the prepared microfiltration membrane will be reduced. At the same time, there is a risk of poloxamer 407 dissolving during the use of the prepared microfiltration membrane, which may reduce cell density and viability when the prepared microfiltration membrane is used for perfusion culture.
[0110] Preferably, by controlling the relative humidity of the air section to 60%-80% and the temperature to 10℃-20℃, the air section first contacts the casting liquid that forms the second surface. When the air humidity is high, the second surface begins to separate phases in the air section. Due to the lower temperature, the phase separation rate is relatively slow. In conjunction with the length of the air section, the formed second surface has relatively small and numerous pores. At the same time, by controlling the coagulation bath temperature to be relatively high, the coagulation bath enters through the pores formed on the second surface at a faster rate. In conjunction with the lower temperature of the core liquid, the thickness of the reinforced layer and the diameter of the reinforced fibers are within the preferred range, and the internal membrane I completes phase separation better within 80s-200s. Furthermore, under the combined effects of the temperature of the coagulation bath, the length of the air section, humidity, and temperature, the pore size of the prepared microfiltration membrane is relatively uniform, that is, the ratio of the initial bubble point of IPA to the complete bubble point of IPA in the microfiltration membrane is within the preferred range.
[0111] A third aspect of the invention provides an application of a polysulfone-based hollow fiber microfiltration membrane for: (a) cell amplification; (b) harvesting of monoclonal antibodies; (c) harvesting of recombinant proteins; (d) harvesting of vaccines; and (e) harvesting of viral vectors.
[0112] Compared with the prior art, the present invention has the following beneficial technical effects:
[0113] 1. This invention scientifically regulates the first surface of a polysulfone-based hollow fiber microfiltration membrane, which is composed of grooved pores and supporting fibers. By controlling the SEM average diameter of the supporting fibers, the ratio of the SEM average diameter of the supporting fibers to the SEM average minor diameter of the grooved pores, the SEM pore size of the flow holes in the grooved pores, and the complete bubble point of the IPA of the microfiltration membrane within a reasonable range, and ensuring that the length direction of the supporting fibers is perpendicular to the length direction of the membrane, the resulting polysulfone-based hollow fiber microfiltration membrane can be used for perfusion culture, and when used for N-1 stage perfusion culture, it achieves high cell density and high cell viability.
[0114] 2. The present invention further improves upon the invention by controlling the initial water contact angle of the first surface and the initial water contact angle of the second surface of the polysulfone hollow fiber microfiltration membrane to be relatively small, i.e. relatively hydrophilic. When the polysulfone hollow fiber microfiltration membrane is used for N-1 stage perfusion culture, the cell density and cell viability are higher, and when used for N-stage perfusion culture, the cell density and cell viability are higher, and the protein retention rate is lower.
[0115] 3. The polysulfone hollow fiber microfiltration membrane of the present invention is integrally formed by casting liquid, which has the advantages of simple preparation method, better manufacturing cost, environmental friendliness and suitability for industrial production. Attached Figure Description
[0116] Figure 1This is a scanning electron microscope (SEM) schematic diagram of the first surface of the polysulfone hollow fiber microfiltration membrane prepared in Example 3, with a magnification of 100×.
[0117] Figure 2 This is a further magnified scanning electron microscope (SEM) schematic diagram of the first surface of the polysulfone hollow fiber microfiltration membrane prepared in Example 3, with a magnification of 2000×.
[0118] Figure 3 This is a scanning electron microscope (SEM) schematic diagram of the cross-section of the polysulfone hollow fiber microfiltration membrane prepared in Example 3, with a magnification of 500×.
[0119] Figure 4 This is a scanning electron microscope (SEM) schematic diagram of the second surface of the polysulfone hollow fiber microfiltration membrane prepared in Example 3, with a magnification of 2000×. Detailed Implementation
[0120] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0121] Example 1
[0122] Step 1: Preparation of casting solution and core solution:
[0123] The casting solution contains the following substances in the following mass percentages: 18.7% polyethersulfone with a weight average molecular weight of 180,000, 68.7% dimethylformamide, 5% PVPK120, 6% PEG200, and 1.6% poloxamer 407.
[0124] The core fluid contains the following substances in the indicated mass percentages: 23.5% ethanol, 76% dimethylformamide, and 0.5% sodium chloride.
[0125] The temperature of the casting solution is 40℃, and the temperature of the core solution is 22℃;
[0126] Step 2: Spinning:
[0127] The casting solution and core solution prepared in step one are extruded together from the spinneret to form a molded product with a first surface and a second surface, wherein the extrusion rate of the core solution is 11 mL / min and the extrusion rate of the casting solution is 8.5 mL / min.
[0128] Step 3: Pre-phase separation:
[0129] The molded product obtained in step two is pre-phase separated in an air section to obtain film I, wherein the length of the air section is 18cm, the relative humidity is 80%, and the temperature is 20℃.
[0130] During the pre-phase separation process, a stretching treatment is performed simultaneously, with a stretching rate of 5%.
[0131] Step 4: Phase Separation
[0132] The biofilm I obtained in step three is immersed in a coagulation bath at 40°C for 80 seconds to form biofilm II. The coagulation bath consists of isopropanol and water, and the mass content of isopropanol is 15%.
[0133] Step 5: Cleaning and drying:
[0134] The biofilm II obtained in step four is washed with pure water and then dried to obtain the polysulfone hollow fiber microfiltration membrane of the present invention.
[0135] Example 2
[0136] Step 1: Preparation of casting solution and core solution:
[0137] The casting solution contains the following substances in the following mass percentages: 17.5% bisphenol A polysulfone with a weight average molecular weight of 190,000, 68% N-methylpyrrolidone, 6% PVPK90, 8% PEG200, and 0.5% poloxamer 407.
[0138] The core fluid contains the following substances in the indicated mass percentages: 27% ethanol, 72% N-methylpyrrolidone, and 1% sodium chloride.
[0139] The temperature of the casting solution is 40℃, and the temperature of the core solution is 24℃;
[0140] Step 2: Spinning:
[0141] The casting solution and core solution prepared in step one are extruded together from the spinneret to form a molded product with a first surface and a second surface, wherein the extrusion rate of the core solution is 12 mL / min and the extrusion rate of the casting solution is 8.5 mL / min.
[0142] Step 3: Pre-phase separation:
[0143] The molded product obtained in step two is pre-phase separated in an air section to obtain film I, wherein the length of the air section is 20cm, the relative humidity is 70%, and the temperature is 16℃.
[0144] During the pre-phase separation process, a stretching treatment is performed simultaneously, with a stretching rate of 8%.
[0145] Step 4: Phase Separation
[0146] The biofilm I obtained in step three is immersed in a coagulation bath at 50°C for 120 seconds to form biofilm II. The coagulation bath consists of isopropanol and water, and the mass content of isopropanol is 18%.
[0147] Step 5: Cleaning and drying:
[0148] The biofilm II obtained in step four is washed with pure water and then dried to obtain the polysulfone hollow fiber microfiltration membrane of the present invention.
[0149] Example 3
[0150] Step 1: Preparation of casting solution and core solution:
[0151] The casting solution contains the following substances in the following mass percentages: 16.8% polyethersulfone with a weight average molecular weight of 150,000, 66.2% dimethylacetamide, 7% PVPK90, 9% PEG400, and 1.0% poloxamer 407.
[0152] The core fluid contains the following substances in the indicated mass percentages: 30.5% isopropanol, 68% dimethylacetamide, and 1.5% lithium chloride.
[0153] The temperature of the casting solution is 50℃, and the temperature of the core solution is 26℃;
[0154] Step 2: Spinning:
[0155] The casting solution and core solution prepared in step one are extruded together from the spinneret to form a molded product with a first surface and a second surface, wherein the extrusion rate of the core solution is 13 mL / min and the extrusion rate of the casting solution is 9 mL / min.
[0156] Step 3: Pre-phase separation:
[0157] The molded product obtained in step two is pre-phase separated in an air section to obtain film I, wherein the length of the air section is 25cm, the relative humidity is 65%, and the temperature is 14℃.
[0158] During the pre-phase separation process, a stretching treatment is performed simultaneously, with a stretching rate of 10%.
[0159] Step 4: Phase Separation
[0160] The biofilm I obtained in step three is immersed in a coagulation bath at 60°C for 160 seconds to form biofilm II. The coagulation bath consists of isopropanol and water, and the mass content of isopropanol is 20%.
[0161] Step 5: Cleaning and drying:
[0162] The biofilm II obtained in step four is washed with pure water and then dried to obtain the polysulfone hollow fiber microfiltration membrane of the present invention.
[0163] Example 4
[0164] Step 1: Preparation of casting solution and core solution:
[0165] The casting solution contains the following substances in the following mass percentages: 15.9% polyphenylsulfone with a weight average molecular weight of 160,000, 64.1% dimethyl sulfoxide, 8% PVPK120, 10% PEG400, and 2.0% poloxamer 407.
[0166] The core fluid contains the following substances in the indicated mass percentages: 34% isopropanol, 64% dimethyl sulfoxide, and 2% lithium chloride.
[0167] The temperature of the casting solution is 60℃, and the temperature of the core solution is 28℃;
[0168] Step 2: Spinning:
[0169] The casting solution and core solution prepared in step one are extruded together from the spinneret to form a molded product with a first surface and a second surface, wherein the extrusion rate of the core solution is 14 mL / min and the extrusion rate of the casting solution is 9.5 mL / min.
[0170] Step 3: Pre-phase separation:
[0171] The molded product obtained in step two is pre-phase separated in an air section to obtain film I, wherein the length of the air section is 30cm, the relative humidity is 60%, and the temperature is 10℃.
[0172] During the pre-phase separation process, a stretching treatment is performed simultaneously, with a stretching rate of 12%.
[0173] Step 4: Phase Separation
[0174] The biofilm I obtained in step three is immersed in a coagulation bath at 70°C for 200 seconds to form biofilm II. The coagulation bath consists of isopropanol and water, and the mass content of isopropanol is 25%.
[0175] Step 5: Cleaning and drying:
[0176] The biofilm II obtained in step four is washed with pure water and then dried to obtain the polysulfone hollow fiber microfiltration membrane of the present invention.
[0177] The polysulfone-based hollow fiber microfiltration membranes prepared in Examples 1-4 have supporting fibers whose length direction is perpendicular to the membrane's length direction, and groove-like pores whose length direction is also perpendicular to the membrane's length direction. The SEM pore size, along the thickness direction from the first surface to the second surface, first increases and then decreases. The structure, porosity, IPA complete bubble point, ratio of initial IPA bubble point to complete IPA bubble point, thickness, water flux, tensile strength, cell density during perfusion culture, cell viability, and protein rejection rate of the polysulfone-based hollow fiber microfiltration membranes prepared in Examples 1-4 were characterized. Specific results are shown in Tables 1-3 below.
[0178] Table 1 - Overall characteristics of hollow fiber microfiltration membranes in Examples 1-4
[0179] sample Example 1 Example 2 Example 3 Example 4 IPA full foaming point / psi 17.6 15.3 13.4 11.2 The ratio of the initial foaming point of IPA to the complete foaming point of IPA 0.89 0.93 0.92 0.86 Porosity / % 61.4 67.2 72.1 79.4 Thickness / μm 111.5 127.3 165.1 195.3 Water flux / LMH / psi 914 1142 1293 1415 Tensile strength / MPa 5.3 5.1 4.7 4.4 Cell density / ×10⁷ cells / mL 13.7 14.5 15.2 15.9 Cell viability / % 97.3 98.1 98.4 98.9 Protein retention rate / % 17.4 18.8 18.4 15.7
[0180] Table 2 - Features of the first surface in Examples 1-4
[0181] sample Example 1 Example 2 Example 3 Example 4 SEM average diameter of supporting fibers / μm 11.2 13.4 15.3 19.7 SEM mean short axis of groove-like pores / μm 17.5 18.8 20.2 24.3 The ratio of the SEM average diameter of the supporting fibers to the SEM average minor diameter of the grooved pores. 0.64 0.71 076 0.81 SEM average major axis of groove-like pores / μm 26.4 38.7 48.3 76.7 The ratio of the SEM mean major axis to the SEM mean minor axis of the grooved pores. 1.51 2.06 2.39 3.16 Pore area ratio of groove-like pores / % 40.7 48.8 51.7 61.2 SEM pore size of the flow-through hole (μm) No more than 5 No more than 5 No more than 5 No more than 5 Initial water contact angle of the first surface / ° 63 79 69 56 SEM average diameter of circulating fibers / μm 0.12 0.17 0.2 0.28 SEM mean short diameter of the flow guide hole / μm 1.1 1.6 2 2.8 The ratio of the SEM mean major diameter to the SEM mean minor diameter of the guide hole. 2.1 2.3 2.2 2.8 Pore area ratio of the guide hole / % 5.4 9.7 12.4 14.3
[0182] Table 3 - Other features of Examples 1-4
[0183] sample Example 1 Example 2 Example 3 Example 4 Initial water contact angle of the second surface / ° 75 86 80 67 Thickness of reinforcement layer / μm 5.4 12.5 18.7 23.9 SEM average diameter of reinforcing fibers / μm 0.16 0.24 0.33 0.57 Pore area ratio of the second surface / % 25.3 34.7 41.9 53.7 SEM average pore size of the pores on the second surface (μm) 0.31 0.49 0.67 0.94
[0184] The results above show that the polysulfone-based hollow fiber microfiltration membranes prepared in Examples 1-4 possess excellent tensile strength, not less than 4.4 MPa, making them suitable for long-term perfusion culture. They also exhibit excellent water flux, exceeding 900 LMH / psi, achieving a cell density of 13 × 10⁻⁶ cells / mL when used in N-stage or N-1-stage perfusion culture. 7 The cell count is above 97%, and the protein retention rate is below 20% when used for N-stage perfusion culture.
[0185] The culture method for N-1 level perfusion in this invention is as follows (taking CHO cell culture and γ-ray irradiation sterilization as an example):
[0186] The prepared polysulfone hollow fiber microfiltration membranes were assembled into hollow fiber microfiltration membrane modules using standard processes and sterilized by gamma ray irradiation. After sterilization, the membrane modules were thoroughly rinsed, and integrity and pressure holding tests were performed sequentially. Only after passing the tests could the modules be connected to the aseptic culture system. Basic culture medium was added to the sterilized bioreactor and preheated to the target culture temperature. The qualified hollow fiber microfiltration membrane modules were connected to the bioreactor piping, and the ATF (Alternating Tangential Flow) system and peristaltic pump were started to ensure thorough wetting of the membrane modules. Before formal culture, the operating parameters of the bioreactor were calibrated, and then CHO cell suspension was inoculated at the set initial inoculation density. The feeding program and ATF system were simultaneously started and adjusted to the target perfusion flow rate to formally commence CHO cell perfusion culture. During the culture process, the cell density and cell viability in the reaction vessel are monitored in real time. When the cell density decreases, the culture is stopped, and the maximum detected cell density is taken as the cell density of the prepared polysulfone hollow fiber microfiltration membrane. The cell viability corresponding to this cell density is the cell viability of the prepared polysulfone hollow fiber microfiltration membrane.
[0187] The N-stage perfusion culture method in this invention is as follows (taking CHO cells expressing IgG protein and γ-ray irradiation sterilization process as an example):
[0188] The prepared polysulfone hollow fiber microfiltration membranes were assembled into hollow fiber microfiltration membrane modules using standard processes and sterilized by gamma ray irradiation. After sterilization, the membrane modules were thoroughly rinsed, and integrity and pressure holding tests were performed sequentially. Only after passing the tests could the modules be connected to the aseptic culture system. Basic culture medium was added to the sterilized bioreactor and preheated to the target culture temperature. The qualified hollow fiber microfiltration membrane modules were connected to the bioreactor pipeline, and the ATF (Alternating Tangential Flow) system and peristaltic pump were started to ensure thorough wetting of the membrane modules. Before formal culture, the various operating parameters of the bioreactor were calibrated, and then CHO cell suspension was inoculated at the set initial inoculation density. The feeding program and ATF system were simultaneously started and adjusted to the target perfusion flow rate to formally commence CHO cell perfusion culture. When the cell density and cell viability reached the cooling trigger threshold, the cooling program was executed to allow the CHO cells to enter the stage of efficient expression of the target protein. The timing of harvesting the feed solution was determined according to the established process specifications and real-time cell status. The cell density and cell viability at which the cell density and cell viability reach the cooling trigger threshold are the cell density and cell viability of the prepared polysulfone hollow fiber microfiltration membrane. The protein retention rate at the time of liquid harvest is the protein retention rate of the prepared polysulfone hollow fiber microfiltration membrane.
[0189] The cell density and cell viability of the sample can be obtained by placing the obtained cell solution sample into an automated cell counter.
[0190] The absorbance of the sample from the reactor after the N-stage perfusion was measured on a biochemical analyzer and was A. 原液 The absorbance of the harvested protein solution sample was measured on a biochemical analyzer and found to be A. 透过 The protein retention rate is 1-A 透过 / A 原液 .
[0191] Example 5
[0192] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3, except that the casting solution in step one included the following substances in the following mass percentages: 16.8% polyethersulfone with a weight average molecular weight of 150,000, 67.2% N-methylpyrrolidone, 7% PVPK90, and 9% PEG400. The resulting polysulfone-based hollow fiber microfiltration membrane had an initial water contact angle of 88° on its first surface and 96° on its second surface. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 5 showed a cell density reduction to 4.7 × 10⁻¹⁰ when used for N-1 stage perfusion culture. 7 The cell count / mL decreased, and the cell viability dropped to 91.2%.
[0193] Example 6
[0194] Polysulfone-based hollow fiber microfiltration membranes were prepared according to the preparation method of Example 3, except that the casting solution in step one included the following substances in the following mass percentages: 16.8% polyethersulfone with a weight average molecular weight of 150,000, 63.2% N-methylpyrrolidone, 7% PVPK90, 9% PEG400, and 4.0% poloxamer 407. The initial water contact angle of the first surface of the resulting polysulfone-based hollow fiber microfiltration membrane was 47°, and the initial water contact angle of the second surface was 54°. Compared with Example 3, the tensile strength of the hollow fiber microfiltration membrane obtained in Example 6 decreased to 3.6 MPa, resulting in a shorter duration of N-stage perfusion culture and a lower cell density of 5.2 × 10⁻⁶. 7 The cell count / mL decreased, and the cell viability dropped to 92.1%.
[0195] Example 7
[0196] Polysulfone-based hollow fiber microfiltration membranes were prepared according to the preparation method in Example 3, except that the casting solution in step one included the following substances by mass: 16.8% polyethersulfone with a weight average molecular weight of 140,000, 66.2% dimethylacetamide, 7% PVPK90, 9% PEG400, and 1.0% poloxamer 407; the core solution included the following substances by mass: 30.5% isopropanol, 67.5% dimethylacetamide, and 2% lithium chloride; the extrusion rate of the core solution in step two was 15 mL / min, and the extrusion rate of the casting solution was 8 mL / min. The stretching rate during the pre-phase separation process in step three was 15%. The final polysulfone hollow fiber microfiltration membrane had a SEM average major axis of 91.4 μm for the grooved pores, an average minor axis of 29.4 μm for the grooved pores, and an average SEM average diameter of 24.7 μm for the supporting fibers. The ratio of the average SEM diameter of the supporting fibers to the SEM minor axis of the grooved pores was 0.84. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 7 had a tensile strength of 3.9 MPa. When used for N-stage perfusion culture, the duration was shorter, and the cell density decreased to 5.9 × 10⁻⁶. 7 The cell count / mL decreased, and the cell viability dropped to 93.1%.
[0197] Example 8
[0198] Polysulfone-based hollow fiber microfiltration membranes were prepared according to the preparation method of Example 3, except that the casting solution in step one included the following substances by mass: 16.8% polyethersulfone with a weight average molecular weight of 200,000, 66.2% dimethylacetamide, 7% PVPK120, 9% PEG400, and 1.0% poloxamer 407; the core solution included the following substances by mass: 30.5% isopropanol, 69% dimethylacetamide, and 0.5% lithium chloride; the extrusion rate of the core solution in step two was 11 mL / min, the extrusion rate of the casting solution was 10 mL / min, and the stretching treatment in step three... The yield was 2%; the final polysulfone hollow fiber microfiltration membrane had an average major axis of 18.3 μm and an average minor axis of 14.7 μm in its grooved pores, with a ratio of 1.24 between the average major and minor axes. The average diameter of the supporting fibers was 8.3 μm, with a ratio of 0.56 between the average diameter of the supporting fibers and the average minor axis of the grooved pores. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 8 had a water flux of 756 LMH / psi, and the cell density decreased to 5.7 × 10⁻⁶ when used for N-stage perfusion culture. 7 The protein retention rate was increased to 35.4% (cells / mL).
[0199] Example 9
[0200] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3, except that the casting solution in step one included the following substances by mass: 16.8% polyethersulfone with a weight average molecular weight of 190,000, 66.2% dimethylacetamide, 7% PVPK120, 9% PEG400, and 1.0% poloxamer 407, and the temperature of the casting solution was 30°C. The core solution included the following substances by mass: 39.2% isopropanol, 60% dimethyl sulfoxide, and 0.8% lithium chloride, and the temperature of the core solution was 1°C. The final polysulfone-based hollow fiber microfiltration membrane had a SEM average major axis of 49.2 μm, an average minor axis of 11.4 μm, and an average diameter of 8.1 μm for the supporting fibers. The ratio of the average major axis to the average minor axis of the grooved pores was 4.32. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 9 had a water flux of 794 LMH / psi, and the cell density decreased to 6.0 × 10⁻⁶ when used for N-stage perfusion culture. 7 The protein retention rate was increased to 29.3% (cells / mL).
[0201] Example 10
[0202] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following components by mass: 15.3% polyethersulfone (weight average molecular weight 150,000), 65.7% dimethyl sulfoxide, 8% PVPK90, 10% PEG400, and 1.0% poloxamer 407. The core solution included the following components by mass: 38.5% ethanol, 60% dimethylacetamide, and 1.5% lithium chloride. The resulting polysulfone-based hollow fiber microfiltration membrane had a SEM average diameter of 0.35 μm for the flow fibers, a porosity of 81.2%, and an IPA bubble point of 8.3 psi. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 10 had a tensile strength of 3.8 MPa, and its cell density decreased to 6.7 × 10⁻⁶ when used in N-stage perfusion culture. 7 cells / mL.
[0203] Example 11
[0204] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following components by mass: 19.7% polyethersulfone (weight average molecular weight 150,000), 67.3% dimethyl sulfoxide, 5% PVPK90, 7% PEG400, and 1.0% poloxamer 407. The core solution included the following components by mass: 18.5% ethanol, 80% dimethylacetamide, and 1.5% lithium chloride. The final polysulfone-based hollow fiber microfiltration membrane had a SEM average diameter of 0.08 μm for the flow fibers, a porosity of 54.3%, and an IPA bubble point of 19.8 psi. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 11 had a water flux of 747 LMH / psi, and when used for N-stage perfusion culture, the cell density decreased to 6.9 × 10⁻⁶. 7 The cell count / mL decreased, cell viability decreased to 93.4%, and protein retention increased by 31.4%.
[0205] Example 12
[0206] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3, except that the casting solution in step one included the following substances by mass: 15.7% polyethersulfone with a weight average molecular weight of 150,000, 65.3% dimethylacetamide, 6% PVPK90, 12% PEG400, and 1.0% poloxamer 407; the core solution included the following substances by mass: 36% isopropanol, 62% dimethylacetamide, and 2% lithium chloride. The temperature was 15℃; the final polysulfone hollow fiber microfiltration membrane had an average short diameter of 3.3 μm for the flow channels, a ratio of the average major diameter to the average minor diameter of the flow channels (SEM) of 1.5, a pore area ratio of 18.1%, and a pore area ratio of 69.2% for the grooved pores; compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 12 had a tensile strength of 4 MPa, and its cell density decreased to 9.1 × 10⁻⁶ when used for N-stage perfusion culture. 7 cells / mL.
[0207] Example 13
[0208] Polysulfone-based hollow fiber microfiltration membranes were prepared according to the preparation method of Example 3, except that the casting solution in step one included the following substances by mass: 19.2% polyethersulfone with a weight average molecular weight of 150,000, 68.8% dimethylacetamide, 6% PVPK90, 5% PEG400, and 1.0% poloxamer 407; the core solution included the following substances by mass: 21% isopropanol, 78% dimethylacetamide, and 1% lithium chloride; the core solution temperature was 35°C; and step three... The pre-phase stretching ratio was 9%; the final polysulfone hollow fiber microfiltration membrane had an average short diameter of 0.8 μm for the flow channels, a ratio of the average major diameter to the average minor diameter of the flow channels (SEM) of 3.6, a pore area ratio of 4.3%, and a pore area ratio of 34.3% for the grooved pores; compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 13 had a water flux of 882 LMH / psi, and the cell density decreased to 8.7 × 10⁻⁶ when used for N-stage perfusion culture. 7 The cell count / mL decreased, and the cell viability dropped to 94.5%.
[0209] Example 14
[0210] Polysulfone-based hollow fiber microfiltration membranes were prepared according to the preparation method of Example 3, except that the die extrusion width in step two was changed. The final thickness of the polysulfone-based hollow fiber microfiltration membrane was 103.4 μm. Compared with Example 3, the tensile strength of the hollow fiber microfiltration membrane obtained in Example 14 was 4.2 MPa, and the cell density decreased to 10.2 × 10⁻⁶ when used for N-stage perfusion culture. 7 cells / mL.
[0211] Example 15
[0212] Polysulfone-based hollow fiber microfiltration membranes were prepared according to the preparation method of Example 3, except that the core liquid temperature in step one was 15°C, the air section length in step three was 15 cm, the relative humidity was 85%, and the temperature was 15°C, the coagulation bath temperature in step four was 30°C, and the die extrusion width in step two was changed. The final polysulfone-based hollow fiber microfiltration membrane had a thickness of 213.4 μm, an IPA complete bubble point of 15.7 psi, and a ratio of IPA initial bubble point to IPA complete bubble point of 0.75. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 15 had a water flux of 814 LMH / psi, and the cell density decreased to 9.9 × 10⁻⁶ when used for N-stage perfusion culture. 7 The cell count / mL decreased, and the cell viability dropped to 93.9%.
[0213] Example 16
[0214] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the core solution in step one included the following components by mass: 18% isopropanol, 80% dimethylacetamide, and 2% sodium chloride; the core solution temperature was 35°C; the relative humidity in the air section of step three was 50% and the temperature was 10°C; and the isopropanol content in the coagulation bath of step four was 30%, and the coagulation bath temperature was 30°C. The final polysulfone-based hollow fiber microfiltration membrane had a reinforcing layer thickness of 28.8 μm, a SEM average diameter of 0.13 μm for the reinforcing fibers, a pore area ratio of 61.6% on the second surface, and a SEM average pore size of 1.21 μm. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 16 had a tensile strength of 4 MPa, a water flux of 852 LMH / psi, and a cell density reduced to 10.5 × 10⁻⁶ cells / mL when used in N-stage perfusion culture. 7 The cell count / mL decreased, cell viability decreased to 94.2%, and protein retention increased to 22.7%.
[0215] Example 17
[0216] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the core solution in step one included the following components by mass: 39.5% isopropanol, 60% dimethylacetamide, and 0.5% lithium chloride; the core solution temperature was 35°C; the relative humidity in the air section of step three was 88% and the temperature was 20°C; and the isopropanol content in the coagulation bath of step four was 10%, and the coagulation bath temperature was 75°C. The final polysulfone-based hollow fiber microfiltration membrane had a reinforcing layer thickness of 4.4 μm, a SEM average diameter of 0.68 μm for the reinforcing fibers, a pore area ratio of 21.9% on the second surface, and a SEM average pore size of 0.26 μm. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Example 17 had a tensile strength of 3.9 MPa, and when used in N-stage perfusion culture, the cell density decreased to 11.6 × 10⁻⁶. 7 The protein retention rate was increased to 23.4% (cells / mL).
[0217] The results from Examples 5-17 show that the initial water contact angle of the first surface or the initial water contact angle of the second surface of the polysulfone hollow fiber microfiltration membrane, or the SEM average major axis of the grooved pores, or the ratio of the SEM average major axis to the SEM average minor axis of the grooved pores, or the SEM average diameter of the flow fibers, or the porosity of the microfiltration membrane, or the SEM average minor axis of the flow guide holes, or the ratio of the SEM average major axis to the SEM average minor axis of the flow guide holes, or the pore area ratio of the flow guide holes... The hollow fiber microfiltration membrane obtained has acceptable tensile strength, is suitable for perfusion culture, and has acceptable water flux. The specific parameters, such as the pore area ratio of the grooved pores, the ratio of the initial bubble point to the complete bubble point of IPA, the thickness of the microfiltration membrane, the thickness of the reinforcing layer, the SEM average diameter of the reinforcing fibers, the pore area ratio of the second surface, or the SEM average pore size of the pores on the second surface, are not within the preferred range. 7 The cell count is above 91% and the cell viability is above 91%; when used for N-stage perfusion culture, the protein retention rate is below 40%.
[0218] Comparative Example 1
[0219] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following substances by mass: 16.8% polyethersulfone with a weight average molecular weight of 180,000, 67.2% dimethylacetamide, 7% PVPK90, and 9% PEG400. The core solution included the following substances by mass: 30.5% isopropanol, 69.3% dimethylacetamide, and 0.2% lithium chloride. The extrusion rate of the core solution and the casting solution in step two was 10 mL / min. The stretching ratio in the pre-phase separation in step three was 1%. The SEM average diameter of the supporting fibers of the final polysulfone-based hollow fiber microfiltration membrane was 6.7 μm, and the ratio of the SEM average diameter of the supporting fibers to the SEM average minor diameter of the grooved pores was 0.7. Compared with Example 3, the tensile strength of the hollow fiber microfiltration membrane obtained in Comparative Example 1 was 2.8 MPa, which was not suitable for perfusion culture.
[0220] Comparative Example 2
[0221] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following components by mass: 16.8% polyethersulfone (weight average molecular weight 120,000), 67.2% dimethylacetamide, 7% PVPK90, and 9% PEG400; the core solution included the following components by mass: 30.5% isopropanol, 67% dimethylacetamide, and 2.5% lithium chloride; the extrusion rate of the core solution in step three was 15 mL / min, the extrusion rate of the casting solution was 7 mL / min, and the stretching ratio in the pre-phase separation in step three was 18%. The final polysulfone-based hollow fiber microfiltration membrane had a SEM average diameter of 29.8 μm, and the ratio of the SEM average diameter of the supporting fibers to the SEM average minor axis of the grooved pores was 0.71. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Comparative Example 2 had a cell density of 1.3 × 10⁻¹⁰ cells when used for N-1 stage perfusion culture. 7 The cell density and cell viability were both too low to be of practical value, with a cell density / mL of 83.4% and a cell viability of 83.4%.
[0222] Comparative Example 3
[0223] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following components by mass: 17.5% polyethersulfone (weight average molecular weight 150,000), 77% dimethylacetamide, 3.5% PVPK90, and 2% PEG400. The extrusion rate of the core solution in step two was 12 mL / min, and the extrusion rate of the casting solution was 11 mL / min. The final polysulfone-based hollow fiber microfiltration membrane had a SEM average diameter of 14.9 μm for the supporting fibers, and the ratio of the SEM average diameter of the supporting fibers to the SEM average minor axis of the grooved pores was 0.96. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Comparative Example 3 had a water flux of 574 LMH / psi and a cell density of 1.6 × 10⁻¹⁰ for N-1 stage perfusion culture. 7 The cell density and cell viability were both too low to be of practical value.
[0224] Comparative Example 4
[0225] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following substances in terms of mass content: 17.5% polyethersulfone with a weight average molecular weight of 150,000, 60.5% dimethylacetamide, 10% PVPK90, and 12% PEG400. The extrusion rate of the core solution in step two was 9 mL / min, and the extrusion rate of the casting solution was 7 mL / min. The SEM average diameter of the supporting fibers of the finally obtained polysulfone-based hollow fiber microfiltration membrane was 13.7 μm, and the ratio of the SEM average diameter of the supporting fibers to the SEM average minor diameter of the grooved pores was 0.43. Compared with Example 3, the tensile strength of the hollow fiber microfiltration membrane obtained in Comparative Example 4 was 2.4 MPa, which was not suitable for perfusion culture.
[0226] Comparative Example 5
[0227] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following substances by mass: 14.2% polyethersulfone with a weight average molecular weight of 150,000, 69.8% dimethylacetamide, 7% PVPK90, and 9% PEG400. The core solution included the following substances by mass: 48.5% isopropanol, 50% dimethylacetamide, and 1.5% lithium chloride. The SEM pore size of the final polysulfone-based hollow fiber microfiltration membrane was greater than 5 μm. Compared with Example 3, the tensile strength of the hollow fiber microfiltration membrane obtained in Comparative Example 5 was 3.1 MPa, which was not suitable for perfusion culture.
[0228] Comparative Example 6
[0229] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the core solution in step one included the following substances by mass: 30.5% isopropanol and 69.5% dimethylacetamide; the extrusion rate of the core solution in step two was 9 mL / min; the extrusion rate of the casting solution was 9 mL / min; and the stretching in step three (pre-phase separation) was omitted. The first surface of the final polysulfone-based hollow fiber microfiltration membrane did not have grooved pores. Compared to Example 3, the water flux of the hollow fiber microfiltration membrane obtained in Comparative Example 6 was 553 LMH / psi, and the cell density for N-1 stage perfusion culture was 1.8 × 10⁻⁶. 7 The cell density and cell viability were both too low to be of practical value, with a cell density / mL of 82.3% and a cell viability of 82.3%.
[0230] Comparative Example 7
[0231] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following components by mass: 21.7% polyethersulfone (weight average molecular weight 150,000), 62.3% dimethylacetamide, 7% PVPK90, and 9% PEG400; the core solution included the following components by mass: 8.5% isopropanol, 90% dimethylacetamide, and 1.5% lithium chloride; and the coagulation bath in step four consisted of water. The final polysulfone-based hollow fiber microfiltration membrane had an IPA complete bubble point of 23.2 psi. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Comparative Example 7 had a water flux of 614 LMH / psi and a cell density of 1.9 × 10⁻¹⁰ for N-1 stage perfusion culture. 7 The cell density and cell viability were both too low to be of practical value, with a cell density / mL of 83.7% and a cell viability of 83.7%.
[0232] Comparative Example 8
[0233] A polysulfone-based hollow fiber microfiltration membrane was prepared according to the preparation method of Example 3. The difference was that the casting solution in step one included the following components by mass: 14% polyethersulfone with a weight average molecular weight of 150,000, 70% dimethylacetamide, 7% PVPK90, and 9% PEG400; the core solution included the following components by mass: 43.5% isopropanol, 55% dimethylacetamide, and 1.5% lithium chloride; and the coagulation bath in step four contained 50% isopropanol. The final polysulfone-based hollow fiber microfiltration membrane had an IPA (instantaneous plasma pressure) of 6.8 psi. Compared to Example 3, the hollow fiber microfiltration membrane obtained in Comparative Example 8 had a tensile strength of 2.9 MPa. It cannot be used for perfusion culture.
[0234] The initial water contact angles of the first surface and the second surface of the polysulfone hollow fiber microfiltration membranes prepared in Comparative Examples 1-8 are similar to those of the first surface and the second surface of the hollow fiber microfiltration membrane prepared in Example 5.
[0235] The results of Comparative Examples 1-8 show that when the prepared polysulfone hollow fiber microfiltration membrane does not contain grooved pores, or the average SEM diameter of the supporting fibers is too small, or the average SEM diameter of the supporting fibers is too large, or the ratio of the average SEM diameter of the supporting fibers to the average SEM minor axis of the grooved pores is too large, or the ratio of the average SEM diameter of the supporting fibers to the average SEM minor axis of the grooved pores is too small, or the pore size of the flow pores is too large, or the complete bubble point of the microfiltration membrane is too large, or the complete bubble point of the microfiltration membrane is too small, the prepared hollow fiber microfiltration membrane can either not be used for perfusion culture, or when used for N-1 stage perfusion culture, the cell density is less than 3 × 10⁻⁶. 7 When the number of cells / mL is below 90%, the cell viability also decreases to below 90%, resulting in low industrial practical value.
[0236] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A polysulfone-based hollow fiber microfiltration membrane, comprising a body, wherein one side of the body is a first surface facing the inner lumen, and the other side of the body is a second surface, characterized in that: The first surface is composed of grooved pores and supporting fibers, wherein the ratio of the SEM average diameter of the supporting fibers to the SEM average minor axis of the grooved pores is 0.55-0.
85. The average diameter of the supporting fibers, as measured by SEM, is 8 μm-25 μm. The groove-shaped cavity has several flow holes, and the SEM pore size of the flow holes is no greater than 5μm; The length direction of the supporting fiber is perpendicular to the length direction of the membrane; The complete bubble point of the microfiltration membrane's IPA is 8 psi-20 psi.
2. The polysulfone-based hollow fiber microfiltration membrane according to claim 1, characterized in that: The initial water contact angle of the first surface is 55°-80°; The initial water contact angle of the second surface is 65°-88°.
3. The polysulfone-based hollow fiber microfiltration membrane according to claim 1 or 2, characterized in that: The ratio of the SEM average major axis of the groove-shaped cavity to the SEM average minor axis of the groove-shaped cavity is 1.5-3.
5. The major axis of the groove-like pores is perpendicular to the length direction of the membrane; The average major axis of the groove-like pores, as measured by SEM, is 25 μm to 80 μm.
4. The polysulfone-based hollow fiber microfiltration membrane according to claim 1 or 2, characterized in that: The groove-like pores also include flow fibers for forming flow holes, and the SEM average diameter of the flow fibers is 0.1μm-0.3μm; The porosity of the microfiltration membrane is 60%-80%.
5. The polysulfone-based hollow fiber microfiltration membrane according to claim 1 or 2, characterized in that: The supporting fiber contains a plurality of flow guide holes, and the SEM average short diameter of the flow guide holes is 1μm-3μm; The ratio of the SEM average major diameter to the SEM average minor diameter of the guide hole is 2-3.
6. The polysulfone-based hollow fiber microfiltration membrane according to claim 5, characterized in that: The perforation area of the guide hole is 5%-15%; The area ratio of the groove-like pores is 40%-65%.
7. The polysulfone-based hollow fiber microfiltration membrane according to claim 1 or 2, characterized in that: The ratio of the initial bubble point of the IPA of the microfiltration membrane to the complete bubble point of the IPA of the microfiltration membrane is 0.85-0.95; The thickness of the microfiltration membrane is 110μm-200μm.
8. The polysulfone-based hollow fiber microfiltration membrane according to claim 1 or 2, characterized in that: The SEM pore size of the microfiltration membrane first increases and then decreases in the thickness direction from the first surface to the second surface. The region where the SEM aperture first increases is a reinforcement layer on the side near the first surface, and the thickness of the reinforcement layer is 5μm-25μm; The reinforcement layer also includes reinforcement fibers for forming pores in the reinforcement layer, wherein the SEM average diameter of the reinforcement fibers is 0.15μm-0.6μm.
9. The polysulfone-based hollow fiber microfiltration membrane according to claim 1 or 2, characterized in that: The porosity of the second surface is 25%-55%; The average pore size of the holes on the second surface, as determined by SEM, is 0.3 μm to 1 μm.
10. The polysulfone-based hollow fiber microfiltration membrane according to claim 1, characterized in that: The microfiltration membrane, when used for cell perfusion culture, achieves a cell density of no less than 3*102. 7 cells / mL, cell viability not less than 90%; The tensile strength of the microfiltration membrane is not less than 3.5 MPa; The water flux of the microfiltration membrane is not less than 700 LMH / psi.
11. A method for preparing a polysulfone-based hollow fiber microfiltration membrane as described in any one of claims 1-10, characterized in that: Includes the following steps: Step 1: Preparation of casting solution and core solution: The casting solution is composed of a sulfone polymer, a first organic solvent, and a first porogen, wherein the sulfone polymer has a mass content of 15%-20%, and the first porogen has a mass content of 5%-8%. The core fluid is composed of fatty alcohol, a second organic solvent, and an inorganic salt, wherein the mass content of the second organic solvent is 60%-80%, and the mass content of the inorganic salt is 0.5%-2%. The first porogen is selected from at least one of PVPK90 and PVPK120; The weight-average molecular weight of the sulfone polymer is 140,000 to 200,000. The fatty alcohol is selected from at least one of isopropanol and ethanol; The inorganic salt is selected from at least one of sodium chloride and lithium chloride; Step 2: Spinning: The casting solution and core solution prepared in step one are extruded together from the spinneret to form a molded product with a first surface and a second surface. The extrusion rate of the core liquid is 10 mL / min-15 mL / min, the extrusion rate of the casting liquid is 8 mL / min-10 mL / min, and the extrusion rate of the casting liquid is less than the extrusion rate of the core liquid. Step 3: Pre-phase separation: The molded product obtained in step two is subjected to pre-phase separation to obtain film I. The pre-phase separation is carried out in an air section with a length of 15cm-40cm. During the pre-phase separation process, a stretching treatment is performed, with a stretching rate of 2%-15%. Step 4: Phase Separation The biofilm I obtained in step three is immersed in a coagulation bath to completely separate phases and form biofilm II. The coagulation bath is composed of isopropanol and water, and the mass content of isopropanol is 10%-30%. Step 5: Cleaning and drying: The membrane II obtained in step four was washed with pure water and then dried to obtain a polysulfone hollow fiber microfiltration membrane.
12. The method for preparing a polysulfone-based hollow fiber microfiltration membrane according to claim 11, characterized in that: The casting solution further comprises poloxamer 407, wherein the mass content of poloxamer 407 is 0.5%-2%; The polysulfone is at least one of bisphenol A polysulfone, polyethersulfone, and polyphenylsulfone.
13. The method for preparing a polysulfone-based hollow fiber microfiltration membrane according to claim 11, characterized in that: The stretching rate in step two is 5%-12%; The temperature of the casting solution is 40℃-60℃; The temperature of the core fluid is 20℃-30℃.
14. The method for preparing a polysulfone-based hollow fiber microfiltration membrane according to claim 11, characterized in that: The casting solution further comprises a second porogen, wherein the second porogen is selected from at least one of PEG200 and PEG400; The mass content of the second pore-forming agent is 6%-10%; The first organic solvent and the second organic solvent are each independently selected from at least one of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.
15. The method for preparing a polysulfone-based hollow fiber microfiltration membrane according to claim 11, characterized in that: The temperature of the coagulation bath is 40℃-70℃; The phase separation time of the biofilm I in the coagulation bath is 80s-200s; The relative humidity of the air section is 60%-80%, and the temperature is 10℃-20℃.
16. An application of a polysulfone-based hollow fiber microfiltration membrane as described in any one of claims 1-10, characterized in that: The microfiltration membrane is used for: (a) Cell expansion; (b) Harvest of monoclonal antibodies; (c) Harvesting of recombinant proteins; (d) The harvest of vaccines; (e) Harvesting of viral vectors.
Citation Information
Patent Citations
Sulfone polymer hollow fiber ultrafiltration membrane, preparation method and application thereof, and assembly with ultrafiltration membrane
CN119607899A
